Distribution patterns and resource assessment of Li, Ga, Ge and U from coal-fired power plants: A case study of Guizhou Province, Southwest China - Kao Tian; Qingfeng Wang; Tianrong He; Zhonggen Li (Journal of Geochemical Exploration, 2026)

Identification of the Nicotianamine synthase (NAS) gene family in wheat (Triticum aestivum L.) and the role of its member TaNAS4-A in Zn and Fe transport - Gang Liu; Yixuan Sun; Pengyuan He; Yibo Wang; Yixuan Zhang; Qingfeng Li; Fenglou Liu; Shuangxi Zhang; Yingxia Zhang; Caixia Liu; Zhangjun Wang (Functional & Integrative Genomics, 2026)

Thermal design and optimization of HIAF′s medical isotope target under extreme heat flux based on a two-way fluid–structure interaction model - Xin Li; Heng Zhang; Zihao Zhang; Jianrong Zhang; Qingfeng Tang; Wei Wang; Yucui Gao; Lei Yang; Yaling Zhang (Annals of Nuclear Energy, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Alterations in the soil micro-food web and phosphorus availability in tropical agroforestry systems - Guangfan Zhou; Qingfeng Wang; Zhaobo Fan; Ying Shan; Guiliang Wang; Miao Chen; Yukun Zou; Qinfen Li; Jinchuang Wang (Applied Soil Ecology, 2026)

U-series and OSL dating of late Pleistocene mammal fossils in Lower Pubu Cave, South China - Jiemei Zhong; Wei Liao; Yanyan Yao; Chun Tian; Guoshan Li; Qingfeng Shao; Xianjiao Ou; Wei Wang (Quaternary International, 2026)

Salt-activated bimetal–phenolic nanoadhesive for broad-spectrum micro- and nanoplastic removal across salinity gradients - Zheng Cai; Qingfeng Yao; Lan Zhao; Yan Cao; Yishuang Li; Xianluo Hu; Jingming Gong (Chemical Engineering Journal, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Reaction kinetics of typical inorganic salts in H2–Air explosion suppression and the synergistic regulation mechanism of multi-elements - Qiuhong Wang; Rui Guo; Zhenmin Luo; Hu Wen; Xianfeng Chen; Wenzhe Mao; Qingfeng Wang; Qiulin Li; Yifan Li (Chemical Engineering Journal, 2026)

The patterns and driving forces of orbital-to millennial-timescales East Asian summer monsoon precipitation variations during the last glaciation - Yi Li; Jingwei Zhang; Xinmiao Chen; Zhi Zhang; Qingfeng Shao; Xinggong Kong; Simin Peng (CATENA, 2026)

Biome-dependent forest GPP responses to compound drought and heat from 2001 to 2023 - Jinping Liu; Yanqun Ren; Qingfeng Hu; Shoukai Chen; Mingzhe Li (Agricultural and Forest Meteorology, 2026)

Coupling mechanism of iron oxidation-precipitation and optimized copper-zinc leaching in ultrasound-assisted oxygen pressure leaching of complex polymetallic chalcopyrite secondary concentrate - Qingfeng Liu; Yalong Liao; Jialei Li; Min Wu (Minerals Engineering, 2026)

Key exposure components and oxidative stress-driven health risks assessment of oil mist generated by metalworking fluids in industrial building environment - Yang Yang; Yilin Li; Yuming Zhang; Yi Wang; Yalin Liu; Ming Liu; Xudong Li; Yifan Qu; Mengdan Qiao; Qingfeng Cao (Journal of Hazardous Materials, 2026)

Corrigendum to “High-performance of starch-protein edible films with interpenetrating networks via reactive extrusion for food milk powder preservation” [Food Chem. 509 (2026) 148621] - Xuliang Wang; Yanxi Wang; Wenya Ma; Kunpeng Qian; Jiahao Zhang; Qingfeng Dong; Min Fan; Li Li (Food Chemistry, 2026)

Lymph node-targeted H2S-self-releasing multifunctional prodrug for the dual remodeling of immunological and redox homeostasis in autoimmune uveitis - Qinjin Dai; Yuelan Wu; Wenbo Geng; Mengna Li; Wanyun Zhang; Yuxian Lai; Pei Zhang; Xiaoyue Zhang; Chunjiang Zhou; Yinuo Wang; Qingfeng Cao; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Design and single-site feasibility test of a trawl-resistant seafloor platform for broadband seismic observation in fishing-intensive shallow waters: a case study from the Bohai Sea - Xianfeng Li; Qingfeng Hua; Yanliang Pei; Chenguang Liu; Kaiben Yu; Yanpeng Zheng (Marine Geophysical Research, 2026)

Combined effects of Chlorella application and reduced nitrogen fertilization on nitrogen use efficiency and crop yield in facility vegetable systems - Guoliang Zhao; Jingyu Sun; Xingcheng Hu; Zhengxi Cai; Chen Li; Qingfeng Chen (Applied Soil Ecology, 2026)

An onboard ultra-rapid orbit determination strategy for LEO satellite utilizing spaceborne GNSS data - Peng Luo; Yezhi Song; Xiaogong Hu; Qingfeng Wu; Jianhua Yang; Kai Li; Chengpan Tang; Changshao Chen (Advances in Space Research, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

A geographic semantic-driven multimodal fusion LCZ framework for revealing inequality in heat exposure among children and elderly - Qiqi Zhu; Yunchang Zhang; Longli Ran; Dongyang Li; Qingfeng Guan (Sustainable Cities and Society, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Fish-gill-inspired hierarchical membranes with charge-repulsion-mediated ion-selective nanostructures for enhanced desalination performance - Yingxue Zhang; Wei Sun; Haoyu Jiang; Qiuxuan Zhou; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2026)

AI-designed crop populations for sustainable intensification - Ning Luo; Junhan Wang; Morten Graversgaard; Renan C. Umburanas; De Li Liu; Qirui Li; Jonathan Storkey; Simon Willcock; Pu Wang; Qingfeng Meng (Trends in Plant Science, 2026)

Contrasting response of the Asian Summer monsoon to bipolar climates and implications for ice core chronology during Marine Isotope Stages 5c-a inferred from stalagmite record, Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Yalan Zeng; Li Wu; Yijia Liang; Gongzhe Chen; Zhenqiu Zhang; Shaohua Yang; Chunsheng Hu; Peng Sun; Qingfeng Shao; et al. (Global and Planetary Change, 2026)

Ultrasensitive and selective detection of metronidazole residues in milk powder using a novel 3D MOF fluorescent sensor - Xuanqi Zhang; Guiling Gao; Xiaoyong Lai; Qin Hou; Yi Li; Zhiyong Teng; Xiaozhong Wang; Xiao Zhang; Qingfeng Yang (Food Chemistry, 2026)

Optimization of fertilization regimes for major crops in the Hetao Irrigation District based on the DNDC model and evaluation of economic benefits - Cong Hou; Haibin Shi; Yan Yan; Qingfeng Miao; Yi Zhao; Sihan Xue; Jiapeng Zhang; Weiping Li (European Journal of Agronomy, 2026)

In situ gas-foaming strategy to construct nitrogen-doped porous hollow carbon spheres for ultra-broadband microwave absorbers - Youjun Jiang; De-Zhuang Wang; Mengqian Zhang; Yuerong Li; Yazhong Chen; Jun Yang; Xianlong Zhang; Qingfeng Liu; Xueping Wu (Chemical Engineering Journal, 2026)

Synergistic mitigation of apple replant disease: Biochar and compound bacterial fertilizer restructure soil microbial communities and promote plant growth - Yawen Gao; Yunheng Jiang; Houshan Wang; Qingfeng Chang; Bingyu Zhang; Mei Wang; Yusong Liu; Li Xiang; Chengmiao Yin; Zhiquan Mao (Applied Soil Ecology, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Ethyl ferulate attenuates allergic asthma via inhibiting macrophage M2 polarization through STAT6/IRF4 pathway - Longlong Ge; Weizhen Chen; Shuguang Han; Huan Yang; Mingchen Du; Shengpeng Li; Xinran Bai; Peilin Zhao; Dan Chen; Qingfeng Pang; Yaxian Wu (Inflammation Research, 2026)

Chloride ions accelerated the removal of naproxen in Cu(II)/peracetic acid system: Promotion of copper cycling through the formation of copper-chloride complexes - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li (Water Research, 2026)

Seep-related carbonates on continental shelves: Distinctive processes and morphologies revealed by the Qiongdongnan Shelf, South China Sea - Hongli Wang; Qiang Zhao; Fangqi Wang; Qingfeng Hua; Qiuhong Xie; Yangting Liu; Chenguang Liu; Yanliang Pei; Xishuang Li; Yikai Feng; Fei Cao (Marine Geology, 2026)

Enhanced removal of organic pollutants and effective suppression of chlorinated/brominated by-products in heat/peroxymonosulfate system by adding sodium percarbonate - Yao Huang; Chenyu Tang; Bingyu Lu; Jianhang Li; Lukai Zhuang; Minfeng Wang; Haoqiang Tan; Qingfeng Cheng; Qingsong Li; Bo Sun; Jing Zou (Journal of Environmental Chemical Engineering, 2026)

Improvement of probiotic tolerance to hyperosmotic environments by whey protein-citrus pectin conjugate: effect on the physicochemical, structural, survival of probiotic microencapsulation - Xuan Lu; Ning Zhang; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

Interfacial engineering of graphene oxide with heterostructure to construct tortuous pathways in polylactic acid multilayers as barrier packaging - Qingfeng Yang; Xiaotong Sun; Dequan Zhang; Ming Tian; Wenxin Wang; Jinkai Pang; Xin Li; Wei Yang; Chengli Hou (Food Packaging and Shelf Life, 2026)

Evolution of plumes from a composite plate–cylinder heat source under buoyancy–shear driven conditions - Ningbin Zhu; Yang Yang; Mengdan Qiao; Yi Wang; Qingfeng Cao; Yong Cui; Yuming Zhang; Sikang Li (Building and Environment, 2026)

Exosomal Protein Biomarkers for Predicting Early Neurological Deterioration Following Intravenous Thrombolysis in Acute Ischemic Stroke - Jiamin Li; Zixin Wang; Yingnan Zhou; Xinyi Wang; Qi Kong; Jiameng Li; Boyi Yuan; Yun Chen; Wan Wang; Jiapeng Zhao; Jinming Sheng; Haiping Zhao; et al. (Translational Stroke Research, 2026)

The effects of endophytic fungal metabolites from Conyza blinii on antioxidant capacity and healthspan in Caenorhabditis elegans - Yixuan Qi; Yujie Jia; Yixin Chen; Hongying Zhu; Yirong Xiao; Zhao Chen; Limin Su; Xinyu Zhang; Wenrong Zhao; Zhengjiang Li; Youpeng Tuo; Tongliang Bu; et al. (Natural Product Research, 2026)

RURBAN-Map: A knowledge-guided framework for nationwide fine-scale urban-rural land use mapping in China - Qiqi Zhu; Dongyang Li; Longli Ran; Yiran Xu; Yong Zhang; Qingfeng Guan (Remote Sensing of Environment, 2026)

Resistance characteristics of irregular exhaust hoods and inverse design based on airflow distribution in rolling mills - Qingfeng Cao; Yang Yang; Zhaolan Zhang; Yi Wang; Kangning Xiong; Yong Cui; Yuming Zhang; Sikang Li; Ning Lei (Journal of Cleaner Production, 2026)

Highly efficient recovery of gold by selective sulfide reduction from chlorine leachate - Qingfeng Ling; Shiwei Zhou; Bo Li; Yonggang Wei; Hua Wang (Journal of Cleaner Production, 2026)

Synergistic optimization of filter bag arrangement and shape for vortex suppression flow equalization and resistance reduction in a straight-through baghouse dust collector - Qingfeng Cao; Yang Yang; Yi Wang; Kangning Xiong; Ningbin Zhu; Yong Cui; Yuming Zhang; Sikang Li (Journal of Cleaner Production, 2026)

A novel biogas liquefaction process adopting dual nitrogen expansion cycle with carbon dioxide pre-cooling - Yanjun Huang; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Huaibin Li (International Journal of Refrigeration, 2026)

Cyclo(Gly-Tyr) alleviates hypercholesterolemia via modulating gut microbiota: critical roles and mechanisms of Bacteroides and Akkermansia - Jingzhi Chen; Zikang Li; Xinhong Wang; Xinyi Li; Manru Chen; Yan Hua; Ziren Su; Jiannan Chen; Qingfeng Xie; Yucui Li (Food Research International, 2026)

Modulation of postmortem glycolysis in pork by electrostatic field: Roles of pyruvate kinase and myofibrillar protein phosphorylation - Yuqian Xu; Dequan Zhang; Martine Schroyen; Xin Li; Qingfeng Yang; Chengli Hou (Food Chemistry, 2026)

Synergizing early maturity and high yields through planting density and lodging-resistant strategy indica–japonica hybrid rice - Wenyu Jin; Lin Li; Qingfeng Song; Xinguang Zhu; Zhongwei Wei (Field Crops Research, 2026)

The Role and Potential Mechanism of Pectin and Pectin Oligosaccharides in Treating Intestinal Inflammation by Regulating Gut Microbiota - Qingfeng Zhang; Xiaoyu Wu; Jingyi Wang; Jiahao Miao; Cunyin Li; Shangyong Li; Ningning He; Jingyi Song (Probiotics and Antimicrobial Proteins, 2026)

Prediction of in situ seafloor sediment sound speed with machine learning - Mujun Chen; Linqing Zhang; Xinfeng Hu; Xiangmei Meng; Guangming Kan; Siyou Tong; Jingqiang Wang; Guanbao Li; Baohua Liu; Qingfeng Hua; Siqi Wu; Xiaobo Zhang (Journal of Oceanology and Limnology, 2026)

A web-based intelligent computing application for critical elements in Chinese coals - Na Xu; Wenze Lin; Pengfei Li; Qingfeng Wang (Earth Science Informatics, 2026)

Influence of varying oxygen transmission rates in heat-shrinkable packaging on the quality of beef during 90 days of chilled storage - Ming Tian; Jintao Jia; Dequan Zhang; Xiaotong Sun; Jiarui Li; Chaoqiao Zhu; Wei Yang; Xin Li; Qingfeng Yang; Chengli Hou (Meat Science, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Enrichment mechanism and clean utilization of sodium-iron in high alkali and high iron coal in Beishan coal Mine, Xinjiang - Jiaxin Li; Hongyang Bai; Wenfeng Wang; Hengyan Liu; Kexin Che; Peng Wang; Qingfeng Lu (Fuel, 2026)

High-performance of starch-protein edible films with interpenetrating networks via reactive extrusion for food milk powder preservation - Xuliang Wang; Yanxi Wang; Wenya Ma; Kunpeng Qian; Jiahao Zhang; Qingfeng Dong; Min Fan; Li Li (Food Chemistry, 2026)

Multi-head attention driven aggregation-differentiation network for probabilistic groundwater depth forecasting and depth-stratified early warning: A multi-site efficient framework - Jing Xu; Siyuan Liu; Jinran Wu; Yuming Mo; Kun Wang; Qingfeng Ji; You-Gan Wang; Ling Li (Environmental Modelling & Software, 2026)

Multi-objective optimization of oxygen transfer and hydrodynamic shear in dual-impeller stirred tanks via integrated computational fluid dynamics and machine learning framework - Qingfeng Gu; Shuoyan Ji; Yongqiang Liu; Yongbo Wang; Junxiong Yu; Zejian Wang; Yingping Zhuang; Chao Li (Bioresource Technology, 2026)

Modelling of lake–land breeze circulation in a diurnal cycle - Qilong Zhong; Jiyun Song; Xiaoxue Wang; Jinhao Zhang; Qingfeng Zhang; Yuguo Li (Building and Environment, 2026)

Gaussian Function Affine Transformation Model: A Bridge Between Laboratory and Downhole Logging NMR in Shale Oil Reservoirs - Junjie Wang; Pengfei Zhang; Weizheng Gao; Wenbiao Li; Nengwu Zhou; Guohui Chen; Qingfeng Li; Chao Liu; Shuangfang Lu (Natural Resources Research, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

Impact performance of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wenli Chen; Zaixian Chen; Wei Li; Yun Niu; Zhaolong Li (Ocean Engineering, 2026)

Effects of anthropogenic activities on soil microbial communities and greenhouse gas fluxes in coastal wetlands of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Zihao Wang; Kun Li; Chenmiao Liu; Chen Li; Zhengxi Cai; Xinkun Zhao; Xinyi Xu; Hongjie Di; Qingfeng Chen (Journal of Environmental Sciences, 2026)

Comprehensive evaluation of reheating methods on pork meatballs: Focusing on physicochemical properties, flavor profiles and their impact on eating quality - Qin Hou; Tianyi Gao; Jiaxin Wu; Yao Li; Qingfeng Ge; Zhuangli Kang (International Journal of Gastronomy and Food Science, 2026)

Low-amplitude structural features in the Baode Block, Ordos basin, China: Quantitative indicators, formation mechanisms, and coalbed methane implications - Fengfeng Du; Yanbin Yao; Yongchen Li; Qingfeng Zhang; Xiaoxiao Sun; Qiang Xu (International Journal of Coal Geology, 2026)

Stabilization mechanisms, cell density, and survival of probiotic encapsulation prepared with thiolated hyaluronic acid-whey protein complex: For potential colon targeting probiotic delivery system - Ning Zhang; Xuan Lu; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

Bio-organic fertilization promotes soil nutrient cycling and reduces CO2 emissions via regulating bacterial communities in vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (European Journal of Soil Biology, 2026)

Progestins as emerging contaminants in soil: An investigation on their pollution characteristics and ecological risks - Qianwen Jiao; Zhenzhen Xu; Yuzhen Liu; Yimin Li; Yifan Zhao; Qingfeng Chen; Xiaoyan Shen (Environmental Research, 2026)

Differential organ-specific toxicity profiling of BDE-209 and its derivative DBDPE in zebrafish - Jiaqi Zhou; Changqing Zhang; Zihan Li; Chao Fan; Qingfeng Zhai; Meihua Zhang (Environmental Pollution, 2026)

Multi-trait analysis to identify key factors influencing wheat lodging resistance and validation of an integrative lodging index - Hao Ren; Qingfeng Dong; Siting Li; Dezheng Liu; Xubin Zhang; Xue Wang; Liang Chen; Yin-Gang Hu (European Journal of Agronomy, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Mechanically robust and flame-resistant cellulose nanofiber aerogels for efficient smoke pollutant adsorption - Yingying Li; Wenjie Xia; Caoxiong Zhuang; Hongfei Hu; Mingdi Kang; Huinan Wang; Lingling Zhu; Hanwei Wang; Qingfeng Sun (Carbohydrate Polymers, 2026)

Keratan sulfate revisited: UPLC–MS/MS-based quantitative profiling reveals structural heterogeneity and deficiency in ocular pathologies - Xinping Wang; Han Zhou; Xi Liang; Yue Li; Shimei Shen; Yuxin Li; Qingfeng Niu; Bi Ning Zhang; Shuying Xu; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2026)

Swell correction for sub-bottom profile data using variational mode decomposition - Yibao Xiao; Xishuang Li; Kai Liu; Qingfeng Hua; Lejun Liu; Chenguang Liu (Marine Geophysical Research, 2026)

Discovering the causal mechanism of day-night extreme heat driven by 2D and 3D urban landscape changes: a case study of Wuhan, China - Yingqiang Zhong; Shaochun Li; Xinmeng Zhou; Xun Liang; Qingfeng Guan (Sustainable Cities and Society, 2026)

The Input / Evaporation inferred by mineral composition and stable isotope and climatic implications in Serling Co sediment of Tibet, China since last deglacial period - Xinghuan Zhu; Liping Zhu; Junbo Wang; Jianting Ju; Minghui Li; Qiangqiang Kou; Qingfeng Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Sulfonamides and their transformation products in the Yellow River Delta, China: Occurrences, source apportionment, and ecological risks - Yimin Li; Qianwen Jiao; Yifan Zhao; Qingyue Xiang; Hongping Wang; Zhenzhen Xu; Qingfeng Chen; Xiaoyan Shen (Environmental Pollution, 2026)

Pressure drop reduction of filter media for oily aerosol: progress and prospects - Yong Cui; Yang Yang; Kangning Xiong; Yi Wang; Qingfeng Cao; Sikang Li; Yuming Zhang (Energy and Buildings, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Mechanisms of growth enhancement in Tartary buckwheat by endophytic fungi: a transcriptomic and metabolomic insight - Qiqi Xie; Yujie Jia; Jiwen Tao; Tongliang Bu; Xinyu Zhang; Yirong Xiao; Qingfeng Li; Zizhong Tang; Lu Zhang; Gonghong Li; Junhua Liao (Plant and Soil, 2026)

Impedance inversion of high-frequency Chirp sub-bottom profiles constrained by borehole data - Linqing Zhang; Xishuang Li; Lejun Liu; Xiangmei Meng; Qingjie Zhou; Kai Liu; Qingfeng Hua; Jingqiang Wang (Marine Georesources & Geotechnology, 2026)

Facilitating redox cycles of copper species by peroxydisulfate in the copper-catalyzed Fenton-like system for enhanced oxidation of organic contaminants - Bingyu Lu; Jianying Wu; Chenyu Tang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li; Jun Ma (Water Research, 2026)

Experimental and numerical study on ice-induced vibration control of jacket-type offshore wind turbine using tuned mass damper - Rui Wang; Jigang Zhang; Zhehao Ma; Qingfeng Yan; Feifei Liu; Zaixian Chen; Wei Li; Yun Niu (Ocean Engineering, 2026)

Macrocyclic Schiff-base covalent organic polymers with synergistic multi-sites for high-temperature iodine/methyl iodide capture - Liang Liu; Zhonglin Ma; Jiaqing Huang; Zhangjie Huang; Jiajia Li; Jinkai Qiu; Ying Zheng; Cheng Lian; Dongyun Chen; Long Chen; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2026)

The adaptation of prehistoric human activities to environmental changes recorded in a lake core on the Tibetan Plateau - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Marco A. Aquino-López; Qiangqiang Kou; Shuyu Pang; Run Zhang; Minghui Li; Xinmiao Lü; Junbo Wang (Global and Planetary Change, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Cost-minimizing alternative dosage regimens of imipenem/cilastatin/relebactam for patients with renal impairment: a pharmacokinetic/pharmacodynamic simulation study - Xiaoping Shi; Donghui Lao; Qing Xu; Xiaoyu Li; Bijue Liu; Qingfeng He; Xiao Zhu; Qianzhou Lv (European Journal of Clinical Pharmacology, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Intensification of Weddell Sea deep water in the southern Scotia Sea since ∼0.4 Ma: Mechanistic links to the mid-Brunhes transition - Qiang Zhao; Hongli Wang; Yanpeng Zheng; Kai Liu; Xishuang Li; Chenguang Liu; Yanliang Pei; Qingfeng Hua; Long Ma; Yonghua Wu; Shulan Ge; Fei Cao; et al. (Quaternary Science Reviews, 2025)

The prolonged weak monsoon event in East Asia and the interhemispheric seesaw: implications for persistent AMOC forcing at the mid-late Holocene transition - Maoxia Li; Weihong Zhang; Shitao Chen; Jianshun Chen; Yifei Wang; Qingfeng Shao; Yongjin Wang (Global and Planetary Change, 2025)

Variable-intensity electrostatic fields inhibit specific spoilage organisms in fresh meat: Mechanisms and antimicrobial efficacy - Su Wang; Debao Wang; Xiangyuan Wen; Yuqian Xu; Dongmei Leng; Qingfeng Yang; Chengli Hou; Xin Li; Dequan Zhang (Food Chemistry, 2025)

Incorporating quercetin nanocrystals in chitosan-polyvinyl alcohol composite film with cinnamon essential oil loaded Pickering emulsions for enhanced controlled release properties - Simin Fan; Dequan Zhang; Qingfeng Yang; Chaoqiao Zhu; Aurore Richel; Marie-Laure Fauconnier; Cheng Li; Ming Tian; Xin Li; Chengli Hou (Food Packaging and Shelf Life, 2025)

Efficient removal of Pb2+ by iron-doped hydroxyapatite: Synthesis, adsorption, kinetics and mechanisms - Yan Li; Yuxia Zhong; Hang Lei; Qingfeng He; Fengchu Liao; Sisi Tang; Mengdi Liu; Yue-Fei Zhang (Environmental Research, 2025)

A carbon-negative aerogel with superior CO₂ capture, flame retardancy, and strength based on a cellulose/MOF three-dimensional network - Huinan Wang; Lingling Zhu; Wenjie Xia; Mingdi Kang; Qianqian Zhou; Weichen Shi; Xinyi Xiang; Qingfeng Sun; Yingying Li (Chemical Engineering Journal, 2025)

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Genome-wide identification of zinc finger-homeodomain (ZF-HD) gene family and expression analysis during abiotic stress in rye - Qingfeng Li; Yuzhao Ren; Jiaohui Long; Zhaoyi Wang; Feifei Dou; Shilei Wang; Chunying Liu; Xiaodong Wang; Caixia Liu; Fenglou Liu; Zhangjun Wang (Genetic Resources and Crop Evolution, 2025)

Evidence for vertical transmission of avian reovirus in chickens - Li Chen; Lijuan Yin; Li Li; Zhiqiang Wu; Jialin Yang; Shenghua Yang; Xuesong Li; Qingfeng Zhou; Zhanxin Wang; Wencheng Lin (Veterinary Microbiology, 2025)

Hydrodynamics knowledge-driven path planning for safety-constrained energy-saving in amphibious unmanned ground vehicles - Jun Luo; Jing Huang; Huayan Pu; Fanglong Wang; Qingfeng Li; Gang Wang; Mingyang Liu (Ocean Engineering, 2025)

Groundwater recharge responses to vadose zone thickness variation and rainfall patterns in arid Mongolian pine plantations - Yanwen Bai; Katsutoshi Seki; Qingfeng Zhang; Yujie Hu; Li Wang (Groundwater for Sustainable Development, 2025)

Mechanistic insights into metformin's anti-hyperuricemic effect: Targeting PPP/DNPB/XOD-mediated purine pathway, purinosome assembly, and gut microbiota homostasis in rats - Qiuxia Yu; Huijun Liao; Wenwen Tan; Lieqiang Xu; Guoshu Lin; Zhixuan Ai; Qingfeng Xie; Yuhong Liu; Yucui Li; Xiaobo Yang; Ziren Su; Guo Ma; et al. (Chemico-Biological Interactions, 2025)

A physics-informed neural network integrating physical mechanisms and experimental data for predicting VOCs emission rates in machining workshops - Mengdan Qiao; Yang Yang; Ningbin Zhu; Yi Wang; Sikang Li; Qingfeng Cao; Yanghui Hou; Bo Qian (Building and Environment, 2025)

Downregulated miR-199a-3p in Preeclamptic Placenta-derived Exosomes from Cord Blood Hinders VEGF-induced Fetal Glomerular Dysplasia Through Inhibiting Akt1(S473) Phosphorylation via Targeting PHLPP2 - Xiaotong Jiang; Mengqi Gu; Yu Xie; Yuchen Li; Qingfeng Lv; Pengzheng Chen; Die Jing; Yu Zhou; Xietong Wang; Lei Li (Stem Cell Reviews and Reports, 2025)

Integrated Analysis of Phenotypic and Hepatic Transcriptomic Profiles Reveals Enhanced Cold Tolerance in Triploid Crucian Carp - Suifei Tao; Zexun Zhou; Shandong Chen; Jialin Cui; Yude Wang; Kaikun Luo; Wei Liu; Qingfeng Liu; Wuhui Li; Shaojun Liu (Fishes, 2025)
Cold stress poses a critical threat to fish survival by triggering metabolic dysfunction, oxidative damage, immune suppression, and apoptosis. However, hybrid polyploid fish triploid crucian carp (3nRCR, 3n = 150) demonstrate superior stress tolerance. In this study, we investigated the cold adaptation mechanisms in different ploidy cyprinid fishes: triploid crucian carp compared to its diploid improved red crucian carp (Carassius auratus red var., RCC, 2n = 100, ♀) and improved allotetraploid (4nAT, 4n = 200, ♂) progenitors. Under controlled cooling, 3nRCR lost equilibrium at a significantly lower temperature (3.2 °C) than RCC (4.0 °C) and 4nAT (4.5 °C), confirming its superior enhanced cold resistance. Histological examination revealed minimal tissue damage in 3nRCR, characterized by reduced gill inflammation and cellular apoptosis. Transcriptomics revealed triploid-specific molecular strategies: 3nRCR uniquely activated retinol metabolism and metabolic rewiring (arginine/proline metabolism, oxidative phosphorylation). Notably, in the immune-related NLR signaling pathway, both nlrp1 and nlrp3 (key inflammasome components) were significantly downregulated in 3nRCR (p

Prefabricated vertical drain alleviating clogging mechanism of soft ground by air-boosted vacuum preloading method - Huayang Lei; Guoqing Tong; Shuangxi Feng; Jiankai Li; Qingfeng Fang (Marine Georesources & Geotechnology, 2025)

Triple-synergistic dual-macrocyclic polysulfates for efficient capture of diverse iodine species - Jiajia Li; Jiaqing Huang; Xiaoyong Xia; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Monsoon and hydroclimate evolution during Heinrich Stadial 3 as revealed by stalagmite from Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Li Wu; Shaohua Yang; Gongzhe Chen; Zhenqiu Zhang; Yijia Liang; Qingfeng Shao; Hai Cheng; R. Lawrence Edwards (Global and Planetary Change, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Nitrogen-doped graphite supported cobalt nanoparticles as excellent ORR/OER/HER trifunctional electrocatalysts - Wenxuan Fan; Xiangmei Tang; Qingfeng Yi; Guang Li (Fuel, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Preparation of a high-strength, antibacterial, and biodegradable bio-based film through amide crosslinking and nano-reinforcement for fruit packaging - Shuguang Yang; Yile Xu; Anbo Pan; Peisheng Li; Wenwu Yang; Qingfeng Sun; Xiaochun Zhang; Yantao Xu (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A triazine-tri-imidazole based cationic covalent organic polymer featuring high recyclability and radiation tolerance for efficient Re(Tc)O4- sequestration - Jiaqing Huang; Xiaoyong Xia; Jiajia Li; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2025)

Conservation and divergence of OsGSTU9 and OsGSTU19 in cadmium detoxification and accumulation in rice - Xuan Chen; Wei Jiang; Di Chang; Qingfeng Zheng; Chunmeng Zhu; Li Hao; Fanrong Zeng; Zhong-Hua Chen; Guang Chen; Yuan Qin; Fenglin Deng (Journal of Hazardous Materials, 2025)

Occurrence, distribution, and potential risk of 61 glucocorticoids in soils in Shandong Province, China - Qianwen Jiao; Yifan Zhao; Yimin Li; Yuzhen Liu; Hongping Wang; Zhenzhen Xu; Qingfeng Chen; Xiaoyan Shen (Environmental Pollution, 2025)

Thiazolyl-conjugated porous polymer-coated CdZnS for synergistic adsorption and photocatalytic degradation of bisphenol A and with enhanced H2O2 production - Wanjun Xu; Yingxue Zhang; Shihong Dong; A.S. Gubin; I.N. Pugacheva; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

Predicting CircRNA-Disease Associations Based on Heterogeneous Graph Neural Network and Knowledge Graph Attribute Mining Attention - Wei Lan; Cong Peng; Hongyu Zhang; Chunling Li; Qingfeng Chen; Xin Xiao; Zhiqiang Wang (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Statistical investigation of marine bacterial extracellular polysaccharides: deciphering the interplay among environmental adaptation, species distribution, and biomedical potential - Yuanyuan Jiang; Shuo Liang; Qingfeng Niu; Chanjuan Liu; Guangli Yu; Guoyun Li (Marine Life Science & Technology, 2025)

Corrigendum to “Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation” [Toxicology and Applied Pharmacology, 499 (2025) 117352] - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Review of biological algal fertilizer technology: Alleviating salinization, sequestering carbon, and improving crop productivity - Siyao Dai; Weiying Feng; Fanhao Song; Tingting Li; Yingru Tao; Fang Yang; Qingfeng Miao; Pengcheng Duan; Haiqing Liao; Haibin Shi; José Manuel Gonçalves; Isabel Maria Duarte (Bioresource Technology, 2025)

Vibration damping and finite element analysis of a 10 MW jacket-type offshore wind turbine - Jigang Zhang; Haodong Sui; Zhehao Ma; Wenli Chen; Qingfeng Yan; Wei Li; Hongjian Xu; Fengbo Yu; Yun Niu; Junxian Zhao (Ocean Engineering, 2025)

An occupational health assessment of dinotefuran exposure in greenhouse vegetable workers: Metabolomic profiling and toxicokinetic analysis - Jiamin Li; Hao Zhang; Ke Zhao; Chengcheng Han; Changjian Li; Lei Fang; Haiyong Jia; Yong Wang; Hanqiu Tang; Qingfeng Zhai; Peng Xue (Journal of Hazardous Materials, 2025)

Novel QTLs/genes affecting single stem elasticity, stem strength, and three lodging indices in bread wheat (Triticum aestivum L.) identified by genome-wide association analysis - Hao Ren; Shan Lu; Siting Li; Qingfeng Dong; Dezheng Liu; Roi Ben-David; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Microbially mediated mechanisms underlie N2O mitigation by bio-organic fertilizer in greenhouse vegetable production system - Lijun Ren; Lili Dong; Guopeng Liang; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Applied Soil Ecology, 2025)

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Correction: Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

A new type of triploid fish derived from female Carassius auratus red var. × male Gobiocypris rarus - Fanglei Liu; Ziyi Huang; Xuanyi Zhang; Bei Li; Lujiao Duan; Jianming Yu; Qizhi Liu; Siyang Huang; Hongwen Liu; Qiuli Liang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

The synergistic effect of vacuum skin packaging and electrospun film on the quality of grass carp (Ctenopharyngodon idellus) surimi during refrigerated storage - Qingfeng Dong; Xiao Wang; Wenya Ma; Li Li (Food Research International, 2025)

Sustainable nanofiber films based on polylactic acid/modified cellulose nanocrystals containing various types of polyphenols, exhibiting antioxidant activity and high stability - Chaoqiao Zhu; Qingfeng Yang; Ming Tian; Wei Yang; Chengjun Min; Simin Fan; Debao Wang; Xin Li; Dequan Zhang; Chengli Hou (Food Chemistry, 2025)

Gels stability by improving the hydrophobic region of casein: Effect of the mogrosides on the structure, microstructure, and antioxidant activities in vitro digestive of the casein acid-induced gel - Yingdi Wang; Kun Sun; Yutong Hu; Yujie Lin; Jiaxuan Li; Qingfeng Ban; Fei Liu (Food Hydrocolloids, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

HMGB1: A New Target for Ischemic Stroke and Hemorrhagic Transformation - Jiamin Li; Zixin Wang; Jiameng Li; Haiping Zhao; Qingfeng Ma (Translational Stroke Research, 2025)
Stroke in China is distinguished by its high rates of morbidity, recurrence, disability, and mortality. The ultra-early administration of rtPA is essential for restoring perfusion in acute ischemic stroke, though it concurrently elevates the risk of hemorrhagic transformation. High-mobility group box 1 (HMGB1) emerges as a pivotal player in neuroinflammation after brain ischemia and ischemia–reperfusion. Released passively by necrotic cells and actively secreted, including direct secretion of HMGB1 into the extracellular space and packaging of HMGB1 into intracellular vesicles by immune cells, glial cells, platelets, and endothelial cells, HMGB1 represents a prototypical damage-associated molecular pattern (DAMP). It is intricately involved in the pathogenesis of atherosclerosis, thromboembolism, and detrimental inflammation during the early phases of ischemic stroke. Moreover, HMGB1 significantly contributes to neurovascular remodeling and functional recovery in later stages. Significantly, HMGB1 mediates hemorrhagic transformation by facilitating neuroinflammation, directly compromising the integrity of the blood–brain barrier, and enhancing MMP9 secretion through its interaction with rtPA. As a systemic inflammatory factor, HMGB1 is also implicated in post-stroke depression and an elevated risk of stroke-associated pneumonia. The role of HMGB1 extends to influencing the pathogenesis of ischemia by polarizing various subtypes of immune and glial cells. This includes mediating excitotoxicity due to excitatory amino acids, autophagy, MMP9 release, NET formation, and autocrine trophic pathways. Given its multifaceted role, HMGB1 is recognized as a crucial therapeutic target and prognostic marker for ischemic stroke and hemorrhagic transformation. In this review, we summarize the structure and redox properties, secretion and pathways, regulation of immune cell activity, the role of pathophysiological mechanisms in stroke, and hemorrhage transformation for HMGB1, which will pave the way for developing new neuroprotective drugs, reduction of post-stroke neuroinflammation, and expansion of thrombolysis time window.

Predicting the Concentrations of Rare Earth Elements and Yttrium in Coal Using Self-Organizing Map - Na Xu; Fei Li; Wei Zhu; Mark A. Engle; Jiapei Kong; Pengfei Li; Qingfeng Wang; Lishan Shen; Robert B. Finkelman; Shifeng Dai (Natural Resources Research, 2025)

Gut bacteria of the fall armyworm, Spodoptera frugiperda, promote host resistance against the toxic effects of lufenuron - Qianqian Li; Renwen Zheng; Jinyuan Zhao; Sihan Lu; Yue Liu; Dongyan Huang; Jinhui Zhang; Lijuan Liu; Xin Zhou; Qingfeng Tang (Journal of Pest Science, 2025)

Knowledge graphs analysis for research on minerals in coal - Pengfei Li; Na Xu; Qingfeng Wang; Yuqing Wang; Fei Li; Wei Zhu; Qing Li (Earth Science Informatics, 2025)

Optimizing landslide susceptibility mapping using integrated forest by penalizing attributes model with ensemble algorithms - Wei Chen; Chao Wang; Xia Zhao; Li Bai; Qingfeng He; Xi Chen; Qifei Zhao; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2025)

Effects of anthropogenic activities on soil microbial community structure and methane anaerobic oxidation rate in coastal wetlands of Yellow River Delta, China - Chenmiao Liu; Zihao Wang; Xia Gao; Kun Li; Lei Yu; Jingyu Sun; Hongjie Di; Xiaoya Xu; Qingfeng Chen (Applied Soil Ecology, 2025)

Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Corrigendum to ‘What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population?’ [Environ. Pollut. 345 (2024) 123499] - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2025)

Toluene-induced framework expansion in carbazole-based porous organic polymers anchored with Cu-ZnIn2S4 for ultrafast azeotropic wastewater recovery - Yingxue Zhang; Xunxun Li; Wanjun Xu; Yuxin Cheng; Shihong Dong; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Root Transcriptome of Wheat Genotypes Under Zinc Sufficient and Deficiency Conditions - Gang Liu; Ming Ma; Zhangjun Wang; Qingfeng Li; Fenglou Liu; Yixuan Sun; Shiping Hu; Caixia Liu (Journal of Plant Growth Regulation, 2025)

Mechanistic model for the cotransport of colloids and radionuclides in saturated porous systems based on the interaction forces between colloids - Qi Tan; Qingfeng Tang; Xinyi Shi; Hongjie Zhao; Shuyang Li; Yuan Chen; Xiaoyan Wei; Zhen Xu; Duoqiang Pan; Wangsuo Wu (Applied Geochemistry, 2025)

The impact of sub-pixel scale urban function on urban heat island: Insights derived from its decomposition - Qingfeng Guan; Yajun Li; Wenjia Huang; Wei Cao; Zhewei Liang; Jie He; Xun Liang (Applied Geography, 2025)

Numerical Study on the Influence of Catamaran Hull Arrangement and Demihull Angle on Calm Water Resistance - Sumin Guo; Xianhe Yang; Hongyu Li; Weizhuang Ma; Qunhong Tian; Qingfeng Ma; Xin Su; Zongsheng Wang (Journal of Marine Science and Engineering, 2025)
This study investigates the WAM-V (Wave Adaptive Modular Vessel) catamaran configuration, focusing on the hydrodynamic interaction between its articulated hulls. The unique hinged connection mechanism induces a relative angular displacement between the demihulls during operation, significantly modifying the calm water resistance characteristics. Such resistance variations critically influence both vessel maneuverability and the operational effectiveness of onboard acoustic detection systems. This study using computational fluid dynamics (CFD) technology, the effects of varying demihull spacing and the angles of the demihulls on resistance were calculated. Numerical simulations were performed using STAR-CCM+, employing the Reynolds-averaged Navier–Stokes equations (RANS) method combined with the k-epsilon turbulence model. The study investigates the free surface and double body viscous flow at different Froude numbers in the range of 0.3 to 0.75. The analysis focuses on the effects of the demihull spacing ratio (BS/LPP, Demihull spacing/Length between perpendiculars) on calm water resistance. Specifically, the resistance coefficient at BS/LPP = 0.2 is on average 14% higher than that at BS/LPP = 0.5. Additionally, the influence of demihull angles on resistance was simulated at BS/LPP = 0.42. The results indicate that inner demihull angles result in higher resistance compared to outer angles, with the maximum increase in resistance being approximately 9%, with specific outer angles effectively reducing resistance. This study provides a scientific basis for optimizing catamaran design and offers valuable insights for enhancing sailing performance.

Effect of hydraulic retention time on advanced nitrogen removal performance in denitrification and partial-denitrification anammox processes: NH4+-N and organic matter from secondary influent as electron donors - Qingfeng Cheng; Jun Li; Wen-Bo Nie; Hui Tian; Lichao Nengzi; Erdeng Du; Mingguo Peng (Journal of Water Process Engineering, 2025)

Variations of Asian summer monsoon and regional hydroclimate between the MIS 7.1 and 6.5 - Xiumin Zhai; Jingwei Zhang; Yi Li; Yijia Liang; Kan Zhao; Qingfeng Shao; Yongjin Wang; Xinggong Kong (Global and Planetary Change, 2025)

Association of PM2.5-bound multiple metals co-exposure with early cardiovascular damage: A panel study in young adults combining metabolomics - Junjie Chen; Qingfeng Zhou; Yingrong Wang; Yuting Wu; Miao Li; Haotian Wang; Guoying Zheng; Yulan Hao; Xiangke Cao; Wenqi Yang; Lei Zhang; Qian Wang (Environmental Pollution, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

Structural performance and design of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wei Li; Zhenhui Song; Fengbo Yu; Yun Niu; Hanyu Song (Ocean Engineering, 2025)

The hygienic insecticide dimefluthrin induced neurodevelopmental deficits and behavioral disorders in zebrafish (Danio rerio) larvae - Ruirui Li; Wenping Xu; Qingfeng Li; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Environmental Research, 2025)

Multi-omics reveals the molecular mechanisms of rapid growth in distant hybrid fish - Xuanyi Zhang; Fanglei Liu; Bei Li; Lujiao Duan; Jianming Yu; Ziyi Huang; SiYang Huang; Hongwen Liu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Biosurfactants are green and versatile enhancers for sustainable treatment of oily sludge: A review - Feng Zhao; Qingfeng Cui; Han Su; Chunyan Li; Mei Dong (Journal of Environmental Chemical Engineering, 2025)

Intelligent identification of coal macerals using improved semi-supervised semantic segmentation methods - Na Xu; Qingfeng Wang; Pengfei Li; Jiapei Kong; Qing Li; Mark A. Engle; James C. Hower; Wei Zhu (International Journal of Coal Geology, 2025)

Large-scale dual-responsive ClO2 controlled-release film for strawberry preservation - Siqi Chen; Wenya Ma; Ying Cao; Kunpeng Qian; Qingfeng Dong; Li Li (Food Chemistry, 2025)

Balancing simulation performance and computational intensity of CA models for large-scale land-use change simulations - Zhewei Liang; Xun Liang; Xintong Jiang; Tingyu Li; Qingfeng Guan (Environmental Modelling & Software, 2025)

Efficient As(III) removal from acidic wastewater by polymorphism control of FeS - Jing Chen; Qingfeng Dong; Jing Li; Chaobo Zhang; Guang Fu; Zhanqing Lu (Journal of Water Process Engineering, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

The soil microclimate and microbial characteristics jointly drive the response of vegetation productivity to changes in snow cover — A global meta-analysis - Qingfeng Xu; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xinhao Li (Science of The Total Environment, 2024)

Occurrences, source apportionment, and potential risks of 55 progestins in surface water of the Yellow River Delta, China - Xiaoyan Shen; Qudi Zhang; Qingyue Xiang; Jiajun Zhao; Yue Cao; Kun Li; Jiayu Song; Zihao Wang; Xinkun Zhao; Qingfeng Chen (Journal of Hazardous Materials, 2024)

Novel fuel-efficient cryogenic carbon capture system for the combustion exhaust of LNG-powered ships - Qingfeng Jiang; Wenqing Duan; Huaibing Li; Hansheng Feng; Wu Du; Jiayang Gu (International Journal of Refrigeration, 2024)

Recognition of dispersed organic matter macerals using YOLOv5m model with convolutional block attention module - Yuanzhe Wu; Qingfeng Lu; Wenfeng Wang; Wenlong Wang; Jiaxin Li; Xinyi Xu; Kexin Che (Fuel, 2024)

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Anti-enterovirus 71 activity of native fucosylated chondroitin sulfates and their derivatives - Qingfeng Niu; Han Zhou; Xiaoyao Ma; Yuanyuan Jiang; Chanjuan Liu; Wei Wang; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2024)

Enhanced nitrogen removal from secondary effluent of municipal wastewater using denitrification filter: Feasibility of refractory organics as a carbon source - Qingfeng Cheng; Hui Tian; Wen-Bo Nie; Jun Li; Yanting Zuo; Lichao Nengzi; Erdeng Du; Mingguo Peng (Bioresource Technology, 2024)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Numerical Simulation of Self-Propelled Dive Motion of a Virtual Mooring Buoy - Hongyu Li; Huijie Cao; Jiayi Xu; Wenxin Li; Qingfeng Ma; Weizhuang Ma (Journal of Marine Science and Engineering, 2024)
To verify the feasibility of the variable wing actuator for a virtual mooring buoy, this paper investigates the self-propelled dive motion of a virtual mooring buoy under hydrostatic variable density conditions using a computational fluid dynamics (CFD) approach. The virtual mooring buoy developed by our research group is used in this study, and the numerical simulation is performed using the Reynolds-averaged Navier–Stokes (RANS) equation and the SST K-Omega turbulence model to capture the turbulent flow. Grid convergence studies were conducted at three grid resolutions to ensure the accuracy of the numerical simulations. The effects of different wing angles on the self-propelled dive motion of the buoy are focused on and analyzed. The results show that the maximum velocity of the buoy in the horizontal direction can reach 0.31 m/s, with a wing angle of −8°, which is about 35% higher than that of 0°, effectively enhancing the buoy’s anti-disturbance capability against the horizontal currents. In addition, this study further analyzes the self-propelled dive motion of the buoy with variable wing angles. The results show that the velocity and attitude of the buoy at any moment are basically the same as those under the corresponding fixed wing angle. This shows that it is possible to change the motion of the buoy by varying the wing angle, verifying the feasibility of the variable wing actuator.

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Innovation of the global international ship registry system: Evolution process and future reforms - Jihong Chen; Jianghao Xu; Qingfeng Zhao; Zeng Yuan; Li Li; Huangziyi Chen; Yinuo Liu; Yuan Xiang (Ocean & Coastal Management, 2024)

Causal inference of urban heat island effect and its spatial heterogeneity: A case study of Wuhan, China - Yingqiang Zhong; Shaochun Li; Xun Liang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Spatial and temporal heterogeneity of soil salinity and ionic coupling relationship under the water-saving renovation of a typical irrigation district in arid and semi-arid areas - Shuya Yang; Qingfeng Miao; Haibin Shi; Yi Zhao; Xiaoyu Liu; Xin Nie; Weiying Feng; José Manuel Gonçalves; Tao Zhang; Yuxin Li; Yuli Luo (Science of The Total Environment, 2024)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

Comparison of drug-induced liver injury risk between propylthiouracil and methimazole: A quantitative systems toxicology approach - Qingfeng He; Min Li; Peiying Ji; Aole Zheng; Li Yao; Xiao Zhu; Jae-Gook Shin; Volker M. Lauschke; Bing Han; Xiaoqiang Xiang (Toxicology and Applied Pharmacology, 2024)

Predicting anion diffusion in bentonite using hybrid machine learning model and correlation of physical quantities - Tao Wu; Junlei Tian; Xiaoqiong Shi; Zhilong Li; Jiaxing Feng; Zhengye Feng; Qingfeng Li (Science of The Total Environment, 2024)

HashGAT-VCA: A vector cellular automata model with hash function and graph attention network for urban land-use change simulation - Qingfeng Guan; Jianfeng Li; Yaqian Zhai; Xun Liang; Yao Yao (Landscape and Urban Planning, 2024)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

Characterization of shale oil and water micro-occurrence based on a novel method for fluid identification by NMR T2 spectrum - Junjie Wang; Shuangfang Lu; Pengfei Zhang; Qingfeng Li; Yajie Yin; Wenbiao Li; Nengwu Zhou; Guohui Chen; Yangjian Yi; Chenxi Wu (Fuel, 2024)

A preliminary result for centralized autonomous orbit determination of gnss constellation and lunar satellite based on inter-satellite link measurements - Peng Luo; Ye-Zhi Song; Jianhua Yang; Xiaogong Hu; Chengpan Tang; Kai Li; Qingfeng Wu (GPS Solutions, 2024)

Relationship between human activities and environmental changes in the southern Tibetan Plateau since the Little Ice Age - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Jiuju Cheng; Marco A. Aquino-López; Run Zhang; Qiangqiang Kou; Xinmiao Lü; Junbo Wang (Science of The Total Environment, 2024)

Microplastics increase the microbial functional potential of greenhouse gas emissions and water pollution in a freshwater lake: A metagenomic study - Tianyu Zhuo; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Yang Li; Yuan Meng; Lifeng Wu; Bin Chen (Environmental Research, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Pure salt expansion behavior in sulfate saline soil under negative temperature conditions - Fengling Ji; Yuansheng Peng; Qingfeng Lv; Wei Li; Jingjing Yu (Cold Regions Science and Technology, 2024)

Global Trends and Networks in Soil Fertility Enhancement Techniques: a Bibliometric Analysis - Zhuangzhuang Feng; Qingfeng Miao; Haibin Shi; Xianyue Li; Jianwen Yan; José Manuel Gonçalves; Dandan Yu; Yan Yan; Weiying Feng (Journal of Soil Science and Plant Nutrition, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Modeling the Subpixel Land-Use Dynamics and Its Influence on Urban Heat Islands: Impacts of Factors and Scale, and Population Exposure Risk - Xun Liang; Song Guo; Chunyang Huang; Bingyu Wang; Yao Xiao; Jie He; Yang Li; Mengmeng Wang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Late Middle Pleistocene micromammals of the Bianfudong paleolithic site, Heqing, western Yunnan - Meijing Chang; Qijun Ruan; Qingfeng Shao; Jianhui Liu; Qiang Li; Xijun Ni (Quaternary International, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

Hybrid chiral nanocellulose-cyanidin composite with pH and humidity response for visual inspection and real-time tracking of shrimp quality and freshness - Yingxuan Feng; Jian Lin; Xinjie Chen; Hao Chai; Linping Tian; Jiayi Zhang; Qingfeng Sun; Yushan Yang; Yingying Li (Food Chemistry, 2024)

Zein and tannic acid hybrid particles improving physical stability, controlled release properties, and antimicrobial activity of cinnamon essential oil loaded Pickering emulsions - Simin Fan; Qingfeng Yang; Debao Wang; Chaoqiao Zhu; Xiangyuan Wen; Xin Li; Aurore Richel; Marie-Laure Fauconnier; Wei Yang; Chengli Hou; Dequan Zhang (Food Chemistry, 2024)

Irrigation scheduling in sand-layered farmland: Evaluation of water and salinity dynamics in the soil by SALTMED-1D model under mulched maize production in Hetao Irrigation District, China - Zhuangzhuang Feng; Qingfeng Miao; Haibin Shi; Xianyue Li; Jianwen Yan; José Manuel Gonçalves; Liping Dai; Weiying Feng (European Journal of Agronomy, 2024)

The key role of myostatin b in somatic growth in fishes derived from distant hybridization - Qingfeng Liu; Lujiao Duan; Bei Li; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Yuqin Shu; Fangzhou Hu; Jingjing Lin; Xiaoxia Xiong; Shaojun Liu (Science China Life Sciences, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Millennial to orbital scale Indian summer monsoon evolution inferred from grain size end-members in Tengchongbeihai wetland, southwestern China - Dongliang Ning; Xiayun Xiao; Suqin Tang; Yuchen Xu; Xiang Kuai; Ying Ge; Jianan Zheng; Longjuan Cheng; Dejun Wan; Qingfeng Jiang; Yanling Li (Quaternary Science Reviews, 2024)

Contribution of mono- and co-culture of Pseudomonas paralactis, Acinetobacter MN21 and Stenotrophomonas maltophilia to the spoilage of chill-stored lamb - Xiangyuan Wen; Dequan Zhang; James D. Morton; Su Wang; Xiaoyu Chai; Xin Li; Qingfeng Yang; Jinhuo Li; Wei Yang; Chengli Hou (Food Research International, 2024)

High strength and water tolerance fish gelatin-xanthan gum acid-induced electrostatic film by melt extrusion method - Xiaohan Chen; Zhuolin Liu; Wenya Ma; Hao Wang; Qingfeng Dong; Li Li (Food Hydrocolloids, 2024)

Acid doped branched poly(biphenyl pyridine) membranes for high temperature proton exchange membrane fuel cells and vanadium redox flow batteries - Ning Shi; Guorui Wang; Qian Wang; Lele Wang; Qingfeng Li; Jingshuai Yang (Chemical Engineering Journal, 2024)

Study on green closed-loop regeneration of waste lithium iron phosphate based on oxalic acid system - Xiaolong Chai; Xiaohua Yu; Qingfeng Shen; Xingbin Li; Yan Lin; Weisong Cai; Ya Yuan (Waste Management, 2024)

Investigation on enhanced oil recovery and CO2 storage efficiency of temperature-resistant CO2 foam flooding - Xin Chen; Qingfeng Zhang; Japan Trivedi; Yiqiang Li; Jianbin Liu; Zheyu Liu; Shun Liu (Fuel, 2024)

Esterified wheat bran: Physicochemical properties, structure and quality improvement of Chinese steamed bread during refrigerated storage - Hua Li; Qingfeng Wu; Yanyan Guo; Ya Dai; Yali Ping; Zhenzhen Chen; Beibei Zhao (Food Chemistry, 2024)

Grafting small organic molecules on donor-acceptor polymers to regulate electron push-pull interactions for efficient H2O2 production - Shuang Zhao; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu; Dongyun Chen (Chemical Engineering Journal, 2024)

A quaternary ammonium cyclodextrin polymer for efficient photocatalytic production of hydrogen peroxide from pure water - Bingshu Jiang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Applications of agent-based models for green development: a systematic review - Qingfeng Meng; Yu Ji; Zhen Li; Xin Hu; Heap-Yih Chong (Environment, Development and Sustainability, 2024)

An electrical conduction model for calcium-bearing shaly sandstone based on the effective medium Hanai-Bruggeman theory - Pengji Zhang; Yu Liang; Buzhou Huang; Fuyan Gou; Yangming An; Qingfeng Li; Hongzheng Li; Ruiyi Han (Acta Geophysica, 2024)

A repertoire of single nucleotide polymorphisms (SNPs) of major fecundity BMPR1B gene among 75 sheep breeds worldwide - Chunna Cao; Qian Zhou; Yuxin Kang; Zhanerke Akhatayeva; Peiyao Liu; Yuheng Bai; Ran Li; Yu Jiang; Qingfeng Zhang; Xianyong Lan; Chuanying Pan (Theriogenology, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

How can the policy combination promote the development of green buildings? ---Analysis based on stage perspective - Xijie Ai; Qingfeng Meng; Heap-Yih Chong; Zhen Li; Tiantian Hao (Journal of Cleaner Production, 2024)

Thermodynamic design and analysis of air-liquefied energy storage combined with LNG regasification system - Qingfeng Jiang; Shiqing Wan; Chongyao Pan; Guozeng Feng; Huaibing Li; Hansheng Feng; Bo Meng; Jiayang Gu; Yunchu Feng (International Journal of Refrigeration, 2024)

In-situ emulsification in low-tension surfactant/polymer systems: Impacts on enhanced oil recovery - Zheyu Liu; Yiqiang Li; Seyed Hossein Hejazi; Xiaoyan Wang; Xin Chen; Huoxin Luan; Qingfeng Hou; Li Liu (Fuel, 2024)

Benthic foraminiferal assemblages in the coastal zone of the yellow river delta: Environmental significance and characteristics of microbial diversity - Shuyang Huang; Qing Li; Xiaohua Qiu; Hong You; Ruimin Lv; Wei Liu; Qingfeng Chen; Tiantian Wang; Jing Zhang; Junjian Ma; Zihao Wang; Shigang Ding (Continental Shelf Research, 2024)

Applicability and sensitivity analysis of vector cellular automata model for land cover change - Yao Yao; Ying Jiang; Zhenhui Sun; Linlong Li; Dongsheng Chen; Kailu Xiong; Anning Dong; Tao Cheng; Haoyan Zhang; Xun Liang; Qingfeng Guan (Computers, Environment and Urban Systems, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

n-Acetylcysteine protects against diazinon-induced histopathological damage and apoptosis in renal tissue of rats - Gaiqin Dong; Qingfeng Li; Chun Yu; Qing Wang; Danhua Zuo; Xiaozhong Li (Toxicological Research, 2024)

Seafloor Sediment Acoustic Properties on the Continental Slope in the Northwestern South China Sea - Guanbao Li; Jingqiang Wang; Xiangmei Meng; Qingfeng Hua; Guangming Kan; Chenguang Liu (Journal of Marine Science and Engineering, 2024)
The acoustic properties of seafloor sediments on continental slopes play a crucial role in underwater acoustic propagation, communication, and detection. To investigate the acoustic characteristics and spatial distribution patterns of sediments on the continental slope, a geoacoustic experiment was conducted in the northwestern South China Sea. The experiment covered two sections: one crossing the shelf and slope in the downslope direction, and the other near the shelf break in the along-slope direction. In situ techniques, sediment sampling, and laboratory measurements were used to acquire data on sediment acoustic properties (such as sound speed and attenuation) and physical properties (including particle composition, density, porosity, and mean grain size). The experimental findings revealed several key points: (1) Acoustic properties of shallow water coarse-grained sediments and deep-sea sediments were higher when measured in the laboratory compared to in situ measurements. (2) Relationships between measured attenuation and physical properties, as well as between sound speed and mean grain size, showed deviations from previous empirical equations. (3) Sediment acoustic and physical properties exhibited significant variations in the downslope direction, while showing gradual variations in the along-slope direction. These variations can be attributed to sedimentary environmental factors such as material sources, hydrodynamic conditions, and water depth.

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

Unrestricted region and scale: Deep self-supervised building mapping framework across different cities from five continents - Qiqi Zhu; Zhen Li; Tianjian Song; Ling Yao; Qingfeng Guan; Liangpei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population? - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2024)

Enhancing carbon fixation and suppressing bacterial chemotaxis through carbon matrix nano-selenium to mitigate emissions of antibiotic resistance genes and virulence factors from chicken manure - Weikun Guan; Lizhi Li; Cheng Zhang; Dexian Zhang; Qingfeng Xing; Dongsheng Guo; Ouyang Hongbing; Haibo Zhang (Chemical Engineering Journal, 2024)

Geomorphic adjustments of channel bars in the braided reach of the lower Yellow river from 1986 to 2018 - Jie Li; Junqiang Xia; Lingzhong Kong; Qingfeng Ji; Linlin Li; Fan chen (CATENA, 2024)

Multiple thermal events recorded in the Acasta Gneiss Complex: Evidence from in-situ dating of zircon, titanite, and apatite - Qingfeng Mei; Jinhui Yang; Jinfeng Sun; Qiuli Li; Shitou Wu; Xiaoxiao Ling; Peng Peng; Hao Wang (Science China Earth Sciences, 2024)

Enhanced Asian hydroclimate instability during early MIS 6.5 - Dianbing Liu; Yongjin Wang; Xinggong Kong; Qingfeng Shao; Yi Li (Quaternary Science Reviews, 2024)

Potential of novel zinc-based nanomaterials on the microbial community, antibiotic resistance genes, and DNA replication in animal manure - Haibo Zhang; Lizhi Li; Gangfu Chen; Nancheng Yin; Jiangao Guo; Xinrui Ni; Yixin Liu; Ke Wu; Weikun Guan; Cheng Zhang; Xiaochun Wu; Shi Wenkai; et al. (Chemical Engineering Journal, 2024)

Environmental-friendly enzyme nanoreactors with high adsorption capacity for long-time and efficient treatment of pollutants under visible light irradiation - Shuting Huang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Communication Management and Data Compression Algorithm Design of BeiDou Transparent Transmission Terminal for Argo Buoy - Hongyu Li; Yanjun Fan; Yicheng Wen; Yanchao Zou; Qingfeng Ma; Shaobo Yang (Journal of Marine Science and Engineering, 2024)
The Argo buoy detects marine environmental data by making profile movements in the ocean and transmits the profile detection data to the shore base through the communication terminal. However, due to the large volume of data collected from profile detections and the continuous operation of the terminal, the remote communication of buoys is characterized by lengthy communication times and significant power consumption. A low-power Beidou transparent transmission terminal is designed to solve these problems in this paper. The terminal performs low-power operation management and power management for terminal remote communication. After the end of a communication process, the microcontroller turns the Beidou module power off and enters STOP mode. Before the next communication process begins, the serial port wakes up the microcontroller, which powers up the Beidou module. Before the remote communication, the microcontroller compacts the profile detection data collected by the buoy to reduce the quantity of remote communication data. In this paper, a variety of data compression methods are used to compare the compression rate, and the best compression method is selected according to the format characteristics of the data. The results show that the Beidou transparent transmission terminal of the Argo buoy can realize low power consumption for remote communication in ocean exploration. The terminal reduces power consumption by 77.282% per communication, and the average number of remote communications for each profile detection data are reduced by 55 times. The low-power Beidou transparent transmission terminal improves the battery life and is conducive to the long-term operation of the buoy.

Estimation of mercury uptake and distinction of corn cultivation in China - Dan Wang; Zhonggen Li; Qingfeng Wang (Science of The Total Environment, 2024)

Occurrence, distribution, and environmental risk of 61 glucocorticoids in surface water of the Yellow River Delta, China - Qingyue Xiang; Xiaoyan Shen; Kun Li; Zihao Wang; Xinkun Zhao; Qingfeng Chen (Science of The Total Environment, 2024)

Oil price volatility and gold prices volatility asymmetric links with natural resources via financial market fluctuations: Implications for green recovery - Yang Li; Qingfeng Du (Resources Policy, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Ultrastrong lightweight nanocellulose-based composite aerogels with robust superhydrophobicity and durable thermal insulation under extremely environment - Yushan Yang; Baokang Dang; Chao Wang; Yipeng Chen; Kaicong Chen; Xinjie Chen; Yingying Li; Qingfeng Sun (Carbohydrate Polymers, 2024)

Research on the interplay between green finance and manufacturing sustainability outcomes: insights for low-carbon economy in the post-COVID-19 era - Qingfeng Meng; Ukoha Kalu Okwara; Zhen Li (Environmental Science and Pollution Research, 2023)

Prediction Model of the Sound Speed of Seafloor Sediments on the Continental Shelf of the East China Sea Based on Empirical Equations - Guangming Kan; Junjie Lu; Xiangmei Meng; Jingqiang Wang; Linqing Zhang; Guanbao Li; Baohua Liu; Qingfeng Hua; Mujun Chen (Journal of Marine Science and Engineering, 2023)
Based on the data of the acoustic and physical properties of seafloor sediments obtained on the continental shelf area of the East China Sea (ECS), prediction equations of the sediment sound speed based on single and dual parameters were established, and the correlation of the sound speed with physical parameters was discussed. The results show that the sediment sound speed (c) is strongly correlated with water content (w), density (ρ), void ratio (e), mean grain size (Mz) and median grain size (Md), and the coefficient of determination R2 of the empirical regression equation is generally greater than 0.80, while the empirical regression equation coefficient of determination R2 of the compression coefficient (a) and compression modulus (E) are slightly lower, with 0.79 and 0.73, respectively. The coefficients of determination of the dual parameter regression equations between sediment sound speed with physical property parameters are generally higher than those of the single parameter equations, which are all higher than 0.90 indicating better prediction performance. The sensitivity of the physical parameters to the sound speed was analyzed, and the result shows that the sequence of sensitivity from high to low influence on sediment sound speed is void ratio, density, compressibility coefficient, median grain size and mean grain size. The prediction equations established in this study are a good extension and supplement to marine geoacoustic models and is of great significance for obtaining the acoustic properties of the seafloor sediments on the shelf of the East China Sea.

Diversification of faunal exploitation strategy and human-climate interaction in Southern China and Southeast Asia during the last deglaciation - Yongxiu Lu; Feng Gao; Yiren Wang; Minmin Ma; Aifeng Zhou; Ruiliang Liu; Hiroki Kikuchi; Lele Ren; Qingfeng Shao; Lin Chen; Yongxiang Xu; Haoran Li; et al. (Quaternary Science Reviews, 2023)

Graphene aerogel-doped CoFe2O4/MoS2 sheets for magnetic oil absorption and the degradation of contaminants - Xin Xiang; Wenxuan Deng; Zhiyi He; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2023)

Lignocellulose/chitosan hybrid aerogel composited with fluorescence molecular probe for simultaneous adsorption and detection of heavy metal pollutants - Congcong An; Ming Zhang; Zhihao Xiao; Qingfeng Yang; Lijuan Feng; Siying Li; Meihui Shi (Journal of Environmental Chemical Engineering, 2023)

Multifunctional chemoreactive nanosonosensitizers exert antitumoral, antibacterial and wound healing effects on malignant peripheral nerve sheath tumors - Wei Wang; Yaling Zheng; Haibo Li; Chengjiang Wei; Luodan Yu; Yihui Gu; Qingfeng Li; Yu Chen; Zhichao Wang (Chemical Engineering Journal, 2023)

Theoretical investigation of outer-sphere adsorption of hydrated yttrium ion on the basal surfaces of kaolinite: A density functional study - Bing Li; Xuefa Shi; Chuanshun Li; Qingfeng Hua; Xinfang Li; Quanshu Yan (Chemical Geology, 2023)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

nZnO-based graphene/graphene oxide compounds inhibit methane metabolic pathways and lower the development of antibiotic resistance genes and virulence factors - Haibo Zhang; Lizhi Li; Qingfeng Xing; Jia Chen; Yihao Fan; Luo Dan; Yuhong Zhong; Yang Wang; Dongsheng Guo; Weikun Guan; Cheng Zhang (Journal of Cleaner Production, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Development of electrospun fish gelatin film containing lauroyl arginate ethyl and its application in large yellow croaker (Pseudosciaena crocea) preservation - Qingfeng Dong; Lan Yang; Leiwen Xiang; Yueliang Zhao; Li Li (Food Control, 2023)

Enhanced VOCs adsorption and oxidation by hydrophobic-layer-modified YMn2O5 mullite catalyst with ultralow single-atom Pt loading - Jiaqin He; Yaru Wang; Xunxun Li; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Fabrication of Supramolecular System Derived from Poly β-cyclodextrin Coupling Quinoline Dderivative and Its Fluorescence Sensing of Zinc Ion in Pure Water Environment - Wenping Zhu; Yinlong Chen; Zengchen Liu; Weijie Yang; Yanxia Li; Yahong Chen; Qingfeng Li; Yali Cui; Baodui Wang (Journal of Fluorescence, 2023)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

Vibrational Responses of an Ultra-Large Cold-Water Pipe for Ocean Thermal Energy Conversion: A Numerical Approach - Jian Tan; Yulong Zhang; Li Zhang; Qingfeng Duan; Chen An; Menglan Duan (Journal of Marine Science and Engineering, 2023)
The transportation of seawater on a grand scale via an ultra-large cold-water pipe situated within the context of ocean thermal energy conversion (OTEC) floating installations inherently presents challenges associated with instability and potential malfunction in the face of demanding operational circumstances. This study endeavors to augment the stability and security of cold-water pipe (CWP) operations by scrutinizing their vibrational attributes across diverse boundary configurations. Initially, we invoke Euler–Bernoulli beam theory to forge the analytical framework and proffer a semi-analytical resolution by utilizing the generalized integral transform technique (GITT). Subsequently, we authenticate the convergence and precision of our proposed approach through comparative analysis with extant theories. Our findings underscore the conspicuous influence of boundary conditions on the convergence of transverse displacement. The influence of internal flow on the transverse displacement and the natural frequency manifests substantial variability under different boundary conditions. Significantly, an escalation in the internal flow velocity triggers a concomitant reduction in the natural frequency, ultimately culminating in instability once the critical velocity threshold is reached. Additionally, the reliance of the transverse displacement and the natural frequency on the clump weight at the bottom is markedly pronounced. Our discoveries propose that pipe stability can be ameliorated by adjusting the clump weight at the bottom. Furthermore, the novel insights obtained through our proposed approach can significantly aid in the early-stage design and analysis of CWP.

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Enhancing maize yield through understanding the novel shoot-root interaction in morphology among hybrids with dense planting - Yupeng Zhu; Su Wang; Yunhao Li; Dan Wei; Ning Luo; Pu Wang; Qingfeng Meng (Field Crops Research, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

Application of machine learning to study the effective diffusion coefficient of Re(VII) in compacted bentonite - Zhengye Feng; Zepeng Gao; Yongjia Wang; Tao Wu; Qingfeng Li (Applied Clay Science, 2023)

Interannual variation in gross ecosystem production and evapotranspiration in a temperate semiarid grassland undergoing vegetation recovery - Xinhao Li; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xin Jia; Yun Tian; Chuan Jin; Xiaoshuai Wei; Xinyue Liu; Hongxian Zhao; Qingfeng Xu; Shaorong Hao (Agricultural and Forest Meteorology, 2023)

Polymorphism of GTF2A1 gene is associated with litter size in sheep - Linxiu Yue; Wenjie Li; Yejun Pan; Xianyong Lan; Qingfeng Zhang; Chuanying Pan (Theriogenology, 2023)

Insecticidal potential of a Consolida ajacis extract and its major compound (ethyl linoleate) against the diamondback moth, Plutella xylostella - Jun Peng; Zihan Chen; Xueqian Chen; Renwen Zheng; Sihan Lu; Muhammad Seyab; Fan Yang; Qianqian Li; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Discovery of acylated isoquercitrin derivatives as potent anti-neuroinflammatory agents in vitro and in vivo - Jie Liu; Ailing Hui; Jinghe Wang; Qingfeng Hu; Shengnan Li; Yuanli Chen; Zeyu Wu; Wencheng Zhang (Chemico-Biological Interactions, 2023)

Pyrite and sulfur-coupled autotrophic denitrification system for efficient nitrate and phosphate removal - Xuzhen Liu; Changsheng Zhao; Tongtong Xu; Wei Liu; Qingfeng Chen; Luzhen Li; Yu Tan; Xiaokai Wang; Yanan Dong (Bioresource Technology, 2023)

Rotary Tillage Combined with Reducing Nitrogen Application Decreased Greenhouse Gas Emission from Rice Fields in South China - Jiashun Zheng; Qingfeng Wu; Fusheng Li (Journal of Soil Science and Plant Nutrition, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Ordered macroporous carbonous skeletons implanted with dual-phase Co/CoFe nanoparticles for boosting electrocatalytic performance - Jun-Xuan Li; Longlong Fan; Qingfeng Hua; Qinghong Geng; Yingying Zhang; Xiaoli Fan; Lian Ma; Chengming Wang; Wei Zhu; Xiao Feng; Cuiling Li (Chemical Engineering Journal, 2023)

Biomimetic porphyrin-modified 3D porous composite material adsorption enhances photocatalytic CO2 reduction and tetracycline oxidative degradation - Mengmeng Wang; Yingxue Zhang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Variation in Sunshine Duration and Related Aerosol Influences at Shangdianzi GAW Station, China: 1958–2021 - Weijun Quan; Zhiqiang Ma; Ziming Li; Xiaolan Li; Yingruo Li; Xiangao Xia; Huaigang Zhou; Hujia Zhao; Zhenfa Wang; Weiwei Pu; Fan Dong; Di He; et al. (Journal of Meteorological Research, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

Flexible and mechanically strong MXene/cellulose-lamellae sheets for electromagnetic interference shielding - Yushan Yang; Kaicong Chen; Baokang Dang; Chao Wang; Yipeng Chen; Ming Liu; Yingying Li; Xiaochun Zhang; Qingfeng Sun (Chemical Engineering Journal, 2023)

Correction to: Answer to “Comments” on “The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats” by Armen Nersesyan et al., https://doi.org/10.1007/s11356-022-23796-x - Yuxin Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2023)

Study on the optimal conditions of ultrasonic strengthening phosphogypsum storage and solidification of CO2 - Yu Ma; Jianjun Sheng; Tianyu Li; Cheng Yang; Qingfeng Xiao; Rulan Yang (Sustainable Chemistry and Pharmacy, 2023)

Melt blending crystallization regulating balanced nanodomains in efficient and scalable coating processed organic solar cells - Anran Wang; Yifei Kang; Chunqing Hou; Rong Li; Yilong Song; Qingfeng Dong (Science Bulletin, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

Metabolism of hydrogen peroxide by Lactobacillus plantarum NJAU-01: A proteomics study - Lei Chen; Rui Liu; Suyun Li; Mangang Wu; Hai Yu; Qingfeng Ge (Food Microbiology, 2023)

Development of organic-inorganic hybrid antimicrobial materials by mechanical force and application for active packaging - Weizhong Zhu; Jiali Chen; Qingfeng Dong; Donglei Luan; Ningping Tao; Shanggui Deng; Li Wang; Yi Hao; Li Li (Food Packaging and Shelf Life, 2023)

Portable smartphone-assisted ratiometric fluorescence sensor for visual detection of glucose - Xiaohui Zhang; Bo Sun; Yunyi Zhang; Qingfeng Zhang; Mahmood Hassan Akhtar; Ming Li; Yuwei Gu; Cong Yu (Analytica Chimica Acta, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

Experimental Study on the Influence of Temperature on Rock Salt Creep - Zhikai Dong; Yinping Li; Haoran Li; Ziheng Wang; Xilin Shi; Xiangsheng Chen; Qingfeng Lu (Rock Mechanics and Rock Engineering, 2023)

Characteristics and health risk assessment of heavy metal pollution in atmospheric particulate matter in different regions of the Yellow River Delta in China - Ting Liu; Changsheng Zhao; Qingfeng Chen; Luzhen Li; Guorui Si; Lei Li; Beibei Guo (Environmental Geochemistry and Health, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Phenological responses of Bactrocera dorsalis (Hendel) to climate warming in China based on long-term historical data - Pumo Cai; Yunzhe Song; Litao Meng; Jia Lin; Mengting Zhao; Qingfeng Wu; Chuanpeng Nie; Yanyan Li; Qinge Ji (International Journal of Tropical Insect Science, 2023)
It is well accepted that the phenology of insects whose life activities are closely related to temperature is changing in response to global climate warming. To investigate the impacts of climate warming on the phenology of Bactrocera dorsalis (Hendel) across large temporal and spatial scales, this study collected historical data on the occurrence and population dynamic of this pest in China, and systematically explored its phenological responses. The results showed a delayed trend for the dates of first occurrence, end occurrence, population initial growth, and population peak of B. dorsalis in China during 40 years, and the changes of the latter two phenological parameters were significant. The mean temperature in spring and summer were the key climatic factors affecting the occurrence and population growth of B. dorsalis in China, respectively. Moreover, the B. dorsalis data in eastern, southern, central, and southwestern China showed spatial heterogeneity of phenological responses to climate warming at a regional scale. B. dorsalis phenology and their changing patterns with climate warming varied by geographical location. This study provides valuable information for future monitoring, prediction, and prevention of the oriental fruit fly in the context of climate warming.

Loofah sac-like three-dimensional interwoven network composed of Van-PEG-MWCNTs for rapid and efficient capture of Staphylococcus aureus - Yu Chen; Yong Liu; Qingfeng Dong; Min Fan; Li Li (Food Bioscience, 2023)

Enhanced remediation of phenanthrene in water and soil by novel biochar-immobilized bacterial microspheres - Kai Wang; Yang Sun; Dongyun Chen; Qingfeng Xu; Najun Li; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

How to effectively prevent alienation behavior of prefabricated construction developers: an optimization analysis of regulatory strategies - Xijie Ai; Qingfeng Meng; Zhen Li; Wenyao Liu (Environmental Science and Pollution Research, 2023)

Evaluating the impact of co-administered drug and disease on ripretinib exposure: A physiologically-based pharmacokinetic modeling approach - Chunyang Pan; Yifan Cheng; Qingfeng He; Min Li; Fengjiao Bu; Xiao Zhu; Xiaoyu Li; Xiaoqiang Xiang (Chemico-Biological Interactions, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

Flame propagation characteristics of methane explosion under different venting conditions - Qiuhong Wang; Songling Jin; Zhenmin Luo; Aiping Dai; Qingfeng Wang; Zhouhao Li (Fuel, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Preparation of N-doped cellulose-based hydrothermal carbon using a two-step hydrothermal induction assembly method for the efficient removal of Cr(VI) from wastewater - Xinkun Zhao; Hongxu Liang; Zihao Wang; Daijia Li; Xiaoyan Shen; Xiaoya Xu; Kun Li; Qingyue Xiang; Yihan Wu; Qingfeng Chen (Environmental Research, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Ni-Mn spinel aerogel catalysts with adsorption induced superior activity for Low-Temperature toluene oxidation - Jiaqin He; Xunxun Li; Yaru Wang; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Jinghui He; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Epoxy-functionalized polyethyleneimine modified epichlorohydrin-cross-linked cellulose aerogel as adsorbents for carbon dioxide capture - Xinjie Chen; Jian Lin; Hanwei Wang; Yushan Yang; Chao Wang; Qingfeng Sun; Xiaoping Shen; Yingying Li (Carbohydrate Polymers, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

An intelligent model for early kick detection based on cost-sensitive learning - Peng Chi; Li Qingfeng; Fu Jianhong; Yang Yun; Zhang Xiaomin; Su Yu; Xu Zhaoyang; Zhong Chengxu; Wu Pengcheng (Process Safety and Environmental Protection, 2023)

Low quantity of Pt loaded onto CeCoOx nanoboxes: Surface–rich reactive oxygen species for catalytic oxidation of toluene - Yunchong Liu; Xunxun Li; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Sulfonate-modified calixarene-based porous organic polymers for electrostatic enhancement and efficient rapid removal of cationic dyes in water - Lechen Tian; Shiyuan Zhou; Jiaojiao Zhao; Qingfeng Xu; Najun Li; Dongyun Chen; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Mechanochemical incorporation of magnesium in iron-based composite surface for efficient hydrogenation of carbon dioxide to light olefin - Haipeng Chen; Ningning Ma; Chenwei Wang; Chenlei Liu; Xiaoyu Zhang; Weiwei Yuan; Wenqiang Li; Shixue Zhou; Qingfeng Yang; Xun Feng (Fuel, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Lead-Free Cs3Bi2Br9 perovskite In-situ growth on 3D Flower-like g-C3N4 microspheres to improve photocatalytic performance - Bingke Xie; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

2.5 V “water in salt” aqueous micro-supercapacitors based on polypyrrole-coated NiCo layered double hydroxides - Xijuan Li; Xukun Wang; Guo Liu; Xinyi Sui; Qingfeng Wu; Xinge Wang; Xueliang Lv; Erqing Xie; Zhengxing Zhang (Chemical Engineering Journal, 2023)

Ice-volume and insolation influences on hydroclimate changes in central eastern China during the antepenultimate glacial period - Quan Wang; Shayue Yuan; Yijia Liang; Kan Zhao; Qingfeng Shao; Zhenqiu Zhang; Junji Zhu; Xinggong Kong; Yongjin Wang; Jianghu Lan; Hai Cheng; Chengwei Xia; et al. (Science China Earth Sciences, 2023)

Pricing and promotion efforts strategies of dual-channel green supply chain considering service cooperation and free-riding between online and offline retailers - Mengwan Li; Miyuan Shan; Qingfeng Meng (Environment, Development and Sustainability, 2022)

Association between environmental phenols and all-cause and cancer mortality - Jing He; Qingfeng Xue; Xin Hua; Quanqing Li; Ziwei Chen; Cindy Zhu; Wenyu Shi (Environmental Science and Pollution Research, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Mechanism of molecules crosstalk and the critical role of jasmonic acid on triterpenoid synthesis in Cyclocarya Paliurus cells under Aspergillus niger elicitor - Meng Wang; Daobang Tang; Qiongqiong Xiong; Jiguang Chen; Xiaoxiang Xu; Qingfeng Zhang; Jingen Li; Xiangju Zhou; Zhongping Yin (Journal of Plant Biochemistry and Biotechnology, 2022)

Shallow groundwater enhances water productivity of maize in arid area - Jialu Dai; Ruiping Li; Qingfeng Miao; Congcong Li; Yaoze Lu; Zhimin Hua (Irrigation Science, 2022)

Sediment Waves on the Western Slope of the Chukchi Rise (Arctic Ocean) and Their Implications for the Paleoenvironment - Qingfeng Hua; Guanbao Li; Qingjie Zhou; Shujiang Li; Tengfei Xu; Baohua Liu; Hongxia Chen (Journal of Marine Science and Engineering, 2022)
Based on multibeam bathymetric data and high-resolution shallow sub-bottom profiles acquired during China’s 10th Arctic Scientific Expedition Cruise in 2019, a sediment wave field was found on the western slope of the Chukchi Rise, in the Arctic Ocean. This sediment wave field developed on the lower slope with water depths of between 1200 m and 1800 m and stretched 15 km in the downslope direction. It comprised several parallel sediment waves, with wavelengths ranging from 700 m to 3400 m and wave heights from 12 m to 70 m. In the vertical direction, well-stratified deposits, tens of meters thick, were affected by sediment waves, which exhibit asymmetric waveforms and upslope migration trends. The morphological and seismostratigraphic characteristics of the sediment waves suggested their genesis as a result of the interaction between the bottom current and seafloor morphology, which was also supported by hydrographical data adjacent to the sediment wave field. It was infered that this bottom current was related to the Arctic Circumpolar Boundary Current, which many researchers suggest flows through the study area.

The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats - Yuxin Li; Mingqing Zhong; Xianzhi He; Ruoyu Zhang; Yu Fu; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2022)

Role of Melatonin in Inducing the Physiological and Biochemical Processes Associated with Heat Stress Tolerance in Tall Fescue (Festuca arundinaceous) - Mohammad Nur Alam; Li Yang; Xue Yi; Qingfeng Wang; Arif Hasan Khan Robin (Journal of Plant Growth Regulation, 2022)

Effect of the presence of various natural organic matters on anodic oxidation of electrified carbon nanotube membrane - Yongbao Chu; Yingxin Li; Xiaoyu Ni; Jinhui Du; Qingfeng Ma; Min Wang; Yan Wang (Environmental Science and Pollution Research, 2022)

Dual-channel recycling e-waste pricing decision under the impact of recyclers’ loss aversion and consumers’ bargaining power - Zhen Li; Jia Zhao; Qingfeng Meng (Environment, Development and Sustainability, 2022)

High-Frequency Dependence of Acoustic Properties of Three Typical Sediments in the South China Sea - Jingqiang Wang; Zhengyu Hou; Guanbao Li; Guangming Kan; Baohua Liu; Xiangmei Meng; Qingfeng Hua; Lei Sun (Journal of Marine Science and Engineering, 2022)
The acoustic characteristics of three fine-grained sediments (silty sand, silt, silty clay) in the South China Sea (SCS) were measured and analyzed at high frequency range of 27–247 kHz. The measurement results show that the sound speed dispersion is a positive linear relation at the measured frequency range, and the attenuation follows nonlinear frequency dependence, α = kfn, where n ranges from 0.59 to 0.85 for the three different sediments in the SCS. The frequency dependence of sound speed and attenuation were compared with the published literature. It was found that for silty clay, clayey silt, silt, and silty sand, the dispersion characteristics of these four sediments are basically consistent; in general, the dispersion of coarse particles is significant, and that of fine particles is weak, and permeability is the key parameter that determines the inflection point of high frequency to low frequency. By modeling these sediments with the Biot–Stoll model, it was found that the Biot–Stoll model can better predict the frequency-dependent characteristics of sound attenuation in a high-frequency band under the matching constraints of sound speed dispersion characteristics, indicating that the Biot–Stoll model has good applicability to different types of sediments in a high-frequency band.

TEAD4 overexpression suppresses thyroid cancer progression and metastasis in vitro by modulating Wnt signaling - Buyong Zhang; Qingqing Wang; Yanting Ji; Xuan Zhang; Lingbo Xue; Qingfeng Shi; Jie Li (Journal of Biosciences, 2022)

Late Cretaceous K-rich rhyolitic crystal tuffs from the Chuduoqu area in Eastern Qiangtang subterrane: evidence for crustal thickening of the central Tibetan Plateau prior to India–Asia collision - Yonggang Sun; Bile Li; Fengyue Sun; Qingfeng Ding; Junlin Dong; Ye Qian; Yujin Li; Zhen Yao (Acta Geochimica, 2022)

The more straw we deep-bury, the more soil TOC will be accumulated: when soil bacteria abundance keeps growing - Jiaqi Li; Xuhong Ye; Jing An; Xinxin Jin; Qingfeng Fan; Hongtao Zou; Yulong Zhang (Journal of Soils and Sediments, 2022)

Fifty years of Quaternary palynology in the Tibetan Plateau - Lingyu Tang; Caiming Shen; Houyuan Lu; Chuanhai Li; Qingfeng Ma (Science China Earth Sciences, 2021)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Late Jurassic adakitic ore-bearing granodiorite porphyry intrusions in the Xiaokele porphyry Cu (–Mo) deposit, Northeast China: implications for petrogenesis and tectonic setting - Yonggang Sun; Bile Li; Zhonghai Zhao; Qingfeng Ding; Fanbo Meng; Xusheng Chen; Ye Qian; Yujin Li (Acta Geochimica, 2021)

Dynamic reward and penalty strategies of green building construction incentive: an evolutionary game theory-based analysis - Qingfeng Meng; Yingying Liu; Zhen Li; Changzhi Wu (Environmental Science and Pollution Research, 2021)

Soil and ambient air mercury as an indicator of coal-fired power plant emissions: a case study in North China - Zhonggen Li; Xufeng Chen; Wenli Liu; Taishan Li; Guangle Qiu; Haiyu Yan; Mingmeng Wang; Ji Chen; Guangyi Sun; Qingfeng Wang; Xinbin Feng (Environmental Science and Pollution Research, 2021)

Predicting the near-field strong ground motion based on uncertainties in asperities: an opportunity to reproduce the characteristics of the 1970 Tonghai earthquake (Ms 7.8) - Zongchao Li; Jize Sun; Xueliang Chen; Guochen Wang; Qingfeng Ding (Journal of Seismology, 2021)

Chelerythrine Ameliorates Pulmonary Fibrosis via Activating the Nrf2/ARE Signaling Pathway - Ling Peng; Li Wen; Qingfeng Shi; Feng Gao; Bin Huang; Changming Wang (Cell Biochemistry and Biophysics, 2021)

Distinct methylome patterns contribute to ecotypic differentiation in the growth of the storage organ of a flowering plant (sacred lotus) - Hui Li; Xingyu Yang; Qingfeng Wang; Jinming Chen; Tao Shi (Molecular Ecology, 2021)
DNA methylation is an epigenetic modification involved in phenotypic diversity, plant development, and environmental responses. However, the mechanisms of DNA methylation underpinning the adaption of lotus ( Nelumbo nucifera ) ecotypes to high and low latitudes remain unsolved, especially adaptive evolution of their storage organs. Tropical and temperate lotus ecotypes have thin and enlarged rhizomes which are adapted to low and high latitudes, respectively. Here, we investigated the DNA methylomes and transcriptomes of rhizomes of the temperate and tropical lotus to address this issue. Compared with that of the tropical lotus, the DNA of the temperate lotus was significantly more hypermethylated, indicating an increase in global DNA methylation in the lotus, with rhizome enlargement. Meanwhile, genes associated with differentially methylated regions in their promoters tended to be differentially expressed between the two ecotypes. Interestingly, the genes with their expression negatively correlated with methylation levels in their promoters and genomic regions displayed significantly higher transposon coverage, while the genes showing a significant positive correlation between expression and methylation showed lesser transposon coverage. Further, we identified that DNA methylation, especially in the promoter region, was significantly correlated with the expression of many starch‐biosynthetic, gibberellin‐, and brassinosteroid‐signalling genes associated with rhizome differentiation. Overall, our study unveiled that distinct global and local methylation patterns between the two lotus ecotypes contribute to their expression differences and adaptive phenotypic divergence of their storage organs, highlighting the role of DNA methylation in shaping the ecotypic differentiation of lotus.

Partitioning behaviors of zinc in eight coal-fired power plants with different fueled coals and air pollution control devices - Xian Zhou; Xinbin Feng; Xiangyang Bi; Xinyu Li; Qingfeng Wang; Shan Li; Tianrong He; Zhonggen Li (Environmental Science and Pollution Research, 2021)

Relationships between the sound speed ratio and physical properties of surface sediments in the South Yellow Sea - Guanbao Li; Jingqiang Wang; Xiangmei Meng; Baohua Liu; Guangming Kan; Guozhong Han; Qingfeng Hua; Yanliang Pei; Lei Sun (Acta Oceanologica Sinica, 2021)

Alpha 1-antichymotrypsin may be a biomarker for the progression of amnestic mild cognitive impairment - Shunjie Liu; Junhao Pan; Ke Tang; Qingfeng Lei; Lu He; Xiaodong Cai; Zhong Li (Acta Neurologica Belgica, 2021)

Design, synthesis and biological evaluation of Schiff’s base derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Jian Shi; Yi Zhou; Keren Wang; Qinge Ma; Rongrui Wei; Qingfeng Li; Yiyang Zhao; Zhanpin Qiao; Shuang Liu; Yumin Leng; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2021)

Tectonic implications of the subduction of the Kyushu-Palau Ridge beneath the Kyushu, southwest Japan - Chenglong Xia; Yanpeng Zheng; Baohua Liu; Qingfeng Hua; Long Ma; Xianfeng Li; Qiuhong Xie (Acta Oceanologica Sinica, 2021)

Characterization, identification and evaluation of a novel wheat-Agropyron cristatum (L.) Gaertn. disomic addition line II-30-5 - Qingfeng Li; Yuqing Lu; Cuili Pan; Zhangjun Wang; Fenglou Liu; Jinpeng Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2020)

Isolation and characterization of a recombinant Muscovy duck parvovirus circulating in Muscovy ducks in South China - Hanqin Shen; Jianfei Huang; Zhuanqiang Yan; Lijuan Yin; Qunhui Li; Qingfeng Zhou; Feng Chen (Archives of Virology, 2020)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Floor failure and roadway deformation induced by contiguous coal seams mining at Huopu Mine - Yuejin Peng; Qingfeng Li (Arabian Journal of Geosciences, 2020)

GelMA combined with sustained release of HUVECs derived exosomes for promoting cutaneous wound healing and facilitating skin regeneration - Danyang Zhao; Zhencheng Yu; Yun Li; Yu Wang; Qingfeng Li; Dong Han (Journal of Molecular Histology, 2020)

The transcription factor VaNAC17 from grapevine (Vitis amurensis) enhances drought tolerance by modulating jasmonic acid biosynthesis in transgenic Arabidopsis - Lingye Su; Linchuan Fang; Zhenfei Zhu; Langlang Zhang; Xiaoming Sun; Yi Wang; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2020)

Correction to: Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2020)

Distribution of water-stable aggregates under soil tillage practices in a black soil hillslope cropland in Northeast China - Lei Yan; Xuexin Jiang; Xiaonan Ji; Liting Zhou; Siying Li; Chen Chen; Peiye Li; Yuanchen Zhu; Tianhao Dong; Qingfeng Meng (Journal of Soils and Sediments, 2020)

Runoff and sediment variation and attribution over 60 years in typical Loess Plateau basins - Qiaoqiao Zhao; Li Wang; Hao Liu; Qingfeng Zhang (Journal of Soils and Sediments, 2019)

Additional application of aluminum sulfate with different fertilizers ameliorates saline-sodic soil of Songnen Plain in Northeast China - Meng Zhou; Xiaobing Liu; Qingfeng Meng; Xiannan Zeng; Jizhou Zhang; Dawei Li; Jie Wang; Weiling Du; Xianfa Ma (Journal of Soils and Sediments, 2019)

Targeted disruption of tyrosinase causes melanin reduction in Carassius auratus cuvieri and its hybrid progeny - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Jia Song; Junmei Liu; Wuhui Li; Yuqin Shu; Min Tao; Chun Zhang; Qinbo Qin; Jing Wang; Shaojun Liu (Science China Life Sciences, 2019)

Extraction Optimization and Characterization of Gelatin from Half-Smooth Tongue Sole ( Cynoglossus semilaevis Gunther) Skin - Yanjie Li; Chunming Tang; Qingfeng He; Xiaodan Li; Ailin Zhang (Journal of Aquatic Food Product Technology, 2019)

The expansion process of a Stellera chamaejasme population in a degraded alpine meadow of Northwest China - Fuyuan Gao; Kaiming Li; Chengzhang Zhao; Heng Ren; Xiaoying Nie; Dongyu Jia; Linfeng Li; Qingfeng Li (Environmental Science and Pollution Research, 2019)

Hydrothermal variations in soils resulting from the freezing and thawing processes in the active layer of an alpine grassland in the Qilian Mountains, northeastern Tibetan Plateau - Qingfeng Wang; Qianqian Yang; Hong Guo; Xiongxin Xiao; Huijun Jin; Lili Li; Tingjun Zhang; Qingbai Wu (Theoretical and Applied Climatology, 2019)

Overexpression of VaWRKY12, a transcription factor from Vitis amurensis with increased nuclear localization under low temperature, enhances cold tolerance of plants - Langlang Zhang; Tingting Zhao; Xiaoming Sun; Yi Wang; Chang Du; Zhenfei Zhu; Duncan Kiragu Gichuki; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Molecular Biology, 2019)

Primary limitation on vegetation productivity shifts from precipitation in dry years to nitrogen in wet years in a degraded arid steppe of Inner Mongolia, northern China - Lei Huang; Dangjun Wang; Luhua Yao; Xiaoting Li; Dengke Wang; Qingfeng Du; Yong Zhang; Xiangyang Hou; Yanjun Guo (Journal of Soils and Sediments, 2019)

Comparative Analysis of Fractional Vegetation Cover Estimation Based on Multi-sensor Data in a Semi-arid Sandy Area - Qiuyu Liu; Tinglong Zhang; Yizhe Li; Ying Li; Chongfeng Bu; Qingfeng Zhang (Chinese Geographical Science, 2019)

Effective degradation of Orange G and Rhodamine B by alkali-activated hydrogen peroxide: roles of HO2− and O2·− - Daiyao Wang; Jing Zou; Huahua Cai; Yixin Huang; Fei Li; Qingfeng Cheng (Environmental Science and Pollution Research, 2019)

L-3-n-Butylphthalide reduces ischemic stroke injury and increases M2 microglial polarization - Fangfang Li; Qingfeng Ma; Haiping Zhao; Rongliang Wang; Zhen Tao; Zhibin Fan; Sijia Zhang; Guangwen Li; Yumin Luo (Metabolic Brain Disease, 2018)

Sound speed dispersion characteristics of three types of shallow sediments in the southern yellow sea - Guangming Kan; Baohua Liu; Jingqiang Wang; Xiangmei Meng; Guanbao Li; Qingfeng Hua; Lei Sun (Marine Georesources & Geotechnology, 2018)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Overexpression of VaWRKY14 increases drought tolerance in Arabidopsis by modulating the expression of stress-related genes - Langlang Zhang; Jun Cheng; Xiaoming Sun; Tingting Zhao; Mingjun Li; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2018)

Marker-assisted backcrossing of lcyE for enhancement of proA in sweet corn - Ruichun Yang; Zhiguang Yan; Qingfeng Wang; Xiaoqin Li; Faqiang Feng (Euphytica, 2018)

Experimental study of the ballast in situ sediment acoustic measurement system in South China Sea - Jingqiang Wang; Guanbao Li; Baohua Liu; Guangming Kan; Zhiwen Sun; Xiangmei Meng; Qingfeng Hua (Marine Georesources & Geotechnology, 2018)

Brucella abortus phosphoglyceromutase and dihydrodipicolinate reductase induce Th1 and Th2-related immune responses - Zhiqiang Li; Hui Zhang; Jinliang Zhang; Li Xi; Guangli Yang; Shuli Wang; Qingfeng Zhou; Xiaogen Zhang; Junbo Zhang (World Journal of Microbiology and Biotechnology, 2018)

Associations of MMP-2 −1306 C/T and MMP-9 −1562 C/T polymorphisms with breast cancer risk among different populations: a meta-analysis - Meng Han; Qingfeng Yang; Kai Feng; Rongping Li; Jia Ren; Liguang Wei (Genes & Genomics, 2017)

Preliminary studies of multi-micro/nanomaterials immobilized on the bamboo timber surface - Chunde Jin; Jingpeng Li; Jin Wang; Huanhuan Zheng; Qingfeng Sun; Shenjie Han; Chenye Yan; Qiufang Yao; Bitao Fan (Journal of the Indian Academy of Wood Science, 2016)

Erratum to: Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Characteristics of pathogenic microorganisms found in 99 cases of conjunctivitis from the Qinghai Tibetan area - Benshan Yang; Xiuyuan Li; Qingfeng Liang; Shaoya Zhang; Shijing Deng (Science China Life Sciences, 2016)

Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2016)

Down-regulation of FBP1 by ZEB1-mediated repression confers to growth and invasion in lung cancer cells - Juan Zhang; Jiangtao Wang; Hui Xing; Qingfeng Li; Qianfeng Zhao; Jing Li (Molecular and Cellular Biochemistry, 2016)

Enhancement of tocopherols in sweet corn by marker-assisted backcrossing of ZmVTE4 - Faqiang Feng; Qingfeng Wang; Chen Liang; Ruichun Yang; Xiaoqin Li (Euphytica, 2015)

Structure elucidation of a galactofuranose-rich heteropolysaccharide from aciduric fungus penicillium purpurogenum JS03-21 - Yin Chen; Wenjun Mao; Hui Wang; Weiming Zhu; Qingfeng Niu; Xubo Fang; Tao Li (Glycoconjugate Journal, 2015)

Fluorescence and HPLC Detection of Hydroxyl Radical by a Rhodamine-Nitroxide Probe and its Application in Cell Imaging - Linying Cao; Qingfeng Wu; Qiang Li; Shijun Shao; Yong Guo (Journal of Fluorescence, 2014)

Diversity of Gene Cassette Promoter Variants of Class 1 Integrons in Uropathogenic Escherichia coli - Quhao Wei; Xiaofei Jiang; Min Li; Gang Li; Qingfeng Hu; Huoxiang Lu; Guoqiang Chen; Yonglie Zhou; Yuan Lu (Current Microbiology, 2013)

Cooperation among Numb, MDM2 and p53 in the development and progression of pancreatic cancer - Weiwei Sheng; Ming Dong; Jianping Zhou; Xin Li; Qingfeng Liu; Qi Dong; Feng Li (Cell and Tissue Research, 2013)

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)

QTL mapping for the tocopherols at milk stage of kernel development in sweet corn - Faqiang Feng; Feng Deng; Peng Zhou; Jianbin Yan; Qingfeng Wang; Ruichun Yang; Xiaoqin Li (Euphytica, 2013)

Closing the yield gap could reduce projected greenhouse gas emissions: a case study of maize production in C hina - Zhenling Cui; Shanchao Yue; Guiliang Wang; Qingfeng Meng; Liang Wu; Zhiping Yang; Qiang Zhang; Shiqing Li; Fusuo Zhang; Xinping Chen (Global Change Biology, 2013)
Although the goal of doubling food demand while simultaneously reducing agricultural environmental damage has become widely accepted, the dominant agricultural paradigm still considers high yields and reduced greenhouse gas ( GHG ) intensity to be in conflict with one another. Here, we achieved an increase in maize yield of 70% in on‐farm experiments by closing the yield gap and evaluated the trade‐off between grain yield, nitrogen (N) fertilizer use, and GHG emissions. Based on two groups of N application experiments in six locations for 16 on‐farm site‐years, an integrated soil‐crop system ( HY ) approach achieved 93% of the yield potential and averaged 14.8 Mg ha −1 maize grain yield at 15.5% moisture. This is 70% higher than current crop ( CC ) management. More importantly, the optimal N rate for the HY system was 250 kg N ha −1 , which is only 38% more N fertilizer input than that applied in the CC system. Both the N 2 O emission intensity and GHG intensity increased exponentially as the N application rate increased, and the response curve for the CC system was always higher than that for the HY system. Although the N application rate increased by 38%, N 2 O emission intensity and the GHG intensity of the HY system were reduced by 12% and 19%, respectively. These on‐farm observations indicate that closing the yield gap alongside efficient N management should therefore be prominent among a portfolio of strategies to meet food demand while reducing GHG intensity at the same time.

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Inhibition of focal adhesion kinase induces apoptosis in human gastric carcinoma cells (SGC-7901) - Jiyou Li; Qingfeng Meng; Yu Sun; Huadong Qing (Molecular Biology Reports, 2013)

Roles of intracellular fibroblast growth factors in neural development and functions - Xu Zhang; Lan Bao; Liu Yang; QingFeng Wu; Shuai Li (Science China Life Sciences, 2012)

Spectroscopic and Molecular Modeling Studies of the Interaction Between 4′-O-(α-L-Oleandrosyl)daunorubicin and Human Serum Albumin and Its Analytical Application - Ruina Huo; Cui Li; Fengling Cui; Guisheng Zhang; Qingfeng Liu; Xiaojun Yao (Journal of Fluorescence, 2012)

A comparison of different optimization algorithms for retrieving aerosol optical depths from satellite data: an example of using a dual-angle algorithm - Xihan Mu; Qingfeng Shen; Zhao-Liang Li; Guangjian Yan; José Antonio Sobrino (International Journal of Remote Sensing, 2011)

A high-efficiency, two-dimensional gel electrophoresis platform for mature leaves of grass pea (Lathyrus sativus L.) - Qingfeng Wu; Chun Li; Lanming Ke; Chengjin Jiao; Jinglong Jiang; Xiaoyan Sun; Fengmin Li; Chongying Wang (Acta Physiologiae Plantarum, 2011)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

An improved reverse transcription loop-mediated isothermal amplification assay for sensitive and specific detection of Newcastle disease virus - Qiang Li; Chunyi Xue; Jianping Qin; Qingfeng Zhou; Feng Chen; Yingzuo Bi; Yongchang Cao (Archives of Virology, 2009)

Matrix porosity calculation in volcanic and dolomite reservoirs and its application - Ning Li; Hongliang Wu; Qingfu Feng; Kewen Wang; Yujiang Shi; Qingfeng Li; Xinping Luo (Applied Geophysics, 2009)

Cloning and Expression of a Clamworm Antimicrobial Peptide Perinerin in Pichia pastoris - Qingfeng Zhou; Mingyue Li; Tao Xi (Current Microbiology, 2009)